Double-sided adhesive sheet for transfer
Patent Information
- Application Number
- CN202180084582.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-05-31
- Filing Date
- 2021-12-15
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2041-12-15
AI Technical Summary
[0026] For the double-sided adhesive sheet for transfer printing of the present invention, the first adhesive layer can receive multiple electronic components that have been cut into single pieces at one time without picking them up individually. In addition, the electronic components received by the first adhesive layer can be installed by transferring them onto a large-area circuit board at one time, thus significantly improving manufacturing efficiency.
Smart Images

Figure CN116783261B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a double-sided adhesive sheet for transfer printing. More specifically, this invention relates to a double-sided adhesive sheet for transfer printing suitable for transferring tiny electronic components such as semiconductor chips. Background Technology
[0002] In the manufacturing process of semiconductor devices, semiconductor wafers are typically cut into single pieces while temporarily fixed on dicing tape. After being cut into single pieces, the semiconductor chip is pushed from the dicing tape side on the back of the wafer using a pusher member, picked up using an adsorption clamp called a collet, and mounted onto a mounting substrate such as a circuit board (e.g., Patent Document 1).
[0003] Existing technical documents
[0004] Patent documents
[0005] Patent Document 1: Japanese Patent Application Publication No. 2019-9203 Summary of the Invention
[0006] The problem that the invention aims to solve
[0007] However, due to advancements in microfabrication technology, semiconductor chips are becoming increasingly miniaturized and thinner, which can sometimes damage them when picked up using chucks. Therefore, the mounting of such miniaturized and thin semiconductor chips requires a weak-contact or non-contact method.
[0008] In addition, the miniaturization and multi-layering of semiconductor devices are also developing, requiring multiple tiny semiconductor chips to be densely mounted on a mounting substrate in a multi-layer manner. There is also the problem of poor efficiency when using clips to mount them individually.
[0009] The present invention was made in view of the above-mentioned problems, and its object is to provide a double-sided adhesive sheet for transfer printing, which is suitable for efficiently mounting micro-electronic components such as semiconductor chips onto a mounting substrate without damaging the micro-electronic components such as semiconductor chips.
[0010] means for solving problems
[0011] To achieve the aforementioned objectives, the inventors conducted in-depth research and discovered that by using a low-adhesion adhesive layer to form a first adhesive layer for receiving micro-electronic components such as semiconductor chips and using a peelable adhesive layer to form a second adhesive layer for temporarily fixing them to a carrier substrate, a double-sided adhesive sheet can be efficiently mounted onto a mounting substrate without damaging the micro-electronic components such as semiconductor chips. This invention is based on these insights.
[0012] That is, the first aspect of the present invention provides a transfer double-sided adhesive sheet obtained by laminating a first adhesive layer, a substrate, and a second adhesive layer in this order. With the transfer double-sided adhesive sheet of the first aspect of the present invention, when mounting tiny and thin electronic components such as semiconductor chips onto a mounting substrate such as a circuit board, the first adhesive layer receives the electronic components instead of picking them up individually using clips or the like. By using the transfer double-sided adhesive sheet of the first aspect of the present invention for mounting electronic components, the first adhesive layer can receive multiple electronic components that have been cut into single pieces at once, eliminating the need for individual picking. Furthermore, the electronic components received by the first adhesive layer can be mounted by transferring them onto a large-area mounting substrate in one go, thus significantly improving manufacturing efficiency.
[0013] On the other hand, the second adhesive layer is an adhesive layer used to temporarily fix the double-sided adhesive sheet for transfer of the first aspect of the present invention onto a substrate (carrier substrate) that serves as a base.
[0014] In the transfer double-sided adhesive sheet of the first aspect of the present invention, the first adhesive layer is an adhesive layer for receiving and holding electronic components, and preferably includes a low-adhesion adhesive layer. From the perspective of reducing the force applied to the electronic components during reception and suppressing damage to the electronic components, the configuration of the first adhesive layer including a low-adhesion adhesive layer is suitable. Furthermore, when the first adhesive layer receives the electronic components in a non-contact manner, for example, by pushing the electronic components using a pin member to peel them off the cutting tape and allow them to fall onto the first adhesive layer, sometimes the electronic components bounce off and cannot be received with high precision. When this occurs, the positional accuracy of the electronic product decreases, and sometimes poor contact occurs. From the perspective of easily capturing the electronic components without bouncing when the first adhesive layer receives them in a non-contact manner, and being received with good positional accuracy, the configuration of the first adhesive layer including a low-adhesion adhesive layer is also suitable. Furthermore, it is also preferable to consider that when the electronic component received by the transfer double-sided adhesive sheet of the first aspect of the present invention is mounted onto the mounting substrate, the electronic component can be easily peeled off from the first adhesive layer.
[0015] Furthermore, in the transfer double-sided adhesive sheet of the first aspect of the present invention, the second adhesive layer is an adhesive layer for temporarily fixing to the carrier substrate, and preferably includes a peelable adhesive layer. From the viewpoint of being able to peel the second adhesive layer from the carrier substrate without contamination such as glue residue, and improving reworkability, the configuration in which the second adhesive layer includes a peelable adhesive layer is preferred.
[0016] In the transfer double-sided adhesive sheet of the first aspect of the present invention, the storage modulus (hereinafter, sometimes referred to as "E'1a") of the first adhesive layer at a frequency of 1 Hz and 25°C, measured using AFM-DMA, is preferably 50 MPa or less. This configuration is preferred from the viewpoint of reliably adhesively bonding the electronic component receiving the first adhesive layer. When E'1a is too high, the adhesion of the electronic component to the first adhesive layer decreases, sometimes resulting in defects such as positional displacement or falling of the electronic component. From the viewpoint of the adhesion of the electronic component to the first adhesive layer, E'1a is preferably 40 MPa or less, more preferably 30 MPa or less. Alternatively, it can be 20 MPa or less, or 10 MPa or less. On the other hand, from the viewpoint of transferability from the first adhesive layer to the circuit board, E'1a is preferably 0.1 MPa or more. When E'1a is too low, the adhesion of the electronic component to the first adhesive layer becomes too high, sometimes impairing the transferability when mounted on the mounting substrate. From the viewpoint of the transferability of electronic components to the mounting substrate, E'1a is preferably 0.2 MPa or more, and more preferably 0.5 MPa or more.
[0017] In the transfer double-sided adhesive sheet of the first aspect of the present invention, the storage modulus (hereinafter, sometimes referred to as "E'1b") of the first adhesive layer at a frequency of 1 kHz and 25°C, measured using AFM-DMA, is preferably 100 MPa or less. This configuration is preferred from the viewpoint that when the electronic component is received in a non-contact manner on the first adhesive layer, the electronic component will not bounce off the surface of the first adhesive layer, and the electronic component can be received with good positional accuracy. When E'1b is too high, when the electronic component is dropped and received without contacting the surface of the first adhesive layer, the electronic component may bounce off the predetermined position or flip over, thereby easily reducing positional accuracy. From the viewpoint of positional accuracy of the electronic component on the first adhesive layer, E'1b is preferably 90 MPa or less, more preferably 80 MPa or less. In addition, it can be 70 MPa or less, 60 MPa or less, 50 MPa or less, 40 MPa or less, 30 MPa or less, and particularly 20 MPa or less. On the other hand, from the viewpoint of transferability from the first adhesive layer to the circuit board, E'1b is preferably 0.5 MPa or higher. If E'1b is too low, the adhesion of the electronic component to the first adhesive layer becomes high, and sometimes the electronic component may become embedded in the first adhesive layer when dropped, thereby impairing the transferability when mounted onto the mounting substrate. From the viewpoint of transferability of the electronic component to the mounting substrate, E'1b is preferably 0.7 MPa or higher, more preferably 1 MPa or higher.
[0018] In the transfer double-sided adhesive sheet of the first aspect of the present invention, the ratio (E'1b / E'1a) of the storage modulus (E'1b) of the first adhesive layer at a frequency of 1 kHz and 25°C measured using AFM-DMA to the storage modulus (E'1a) of the first adhesive layer at a frequency of 1 Hz and 25°C measured using AFM-DMA is preferably greater than 1. This configuration is preferred from the viewpoint of improving the balance of adhesiveness, positional accuracy, and transferability of electronic components on the first adhesive layer. From the viewpoint of balancing adhesiveness, positional accuracy, and transferability of electronic components on the mounting substrate, E'1b / E'1a is preferably 1.05 or more, more preferably 1.1 or more. There is no particular upper limit to E'1b / E'1a, but from the viewpoint of the above balance, it is preferably 3 or less.
[0019] In the double-sided adhesive sheet for transfer according to the first aspect of the present invention, the loss modulus (hereinafter, sometimes referred to as "E"1a") of the first adhesive layer at a frequency of 1 Hz and 25°C, as measured using AFM-DMA, is preferably 7 MPa or less. This configuration is preferred from the viewpoint of excellent transferability of electronic components to the mounting substrate. If E"1a is too high, the adhesion of the electronic components to the first adhesive layer becomes too high, which may sometimes impair the transferability when mounted to the mounting substrate. From the viewpoint of transferability of electronic components to the mounting substrate, E"1a is preferably 5 MPa or less, more preferably 3 MPa or less. When E"1a is too low, the adhesion of the electronic components to the first adhesive layer decreases, which may sometimes cause defects such as misalignment or falling of the electronic components. From the viewpoint of adhesion of electronic components to the first adhesive layer, E"1a is preferably 0.01 MPa or more, more preferably 0.03 MPa or more.
[0020] In the transfer double-sided adhesive sheet of the first aspect of the present invention, the adhesion of the first adhesive layer to the stainless steel plate (5 mm in diameter) is preferably 10 gf / Φ5 mm SUS to 250 gf / Φ5 mm SUS. From the viewpoint of the adhesiveness and positional accuracy of the electronic components on the first adhesive layer, a configuration with an adhesion of 10 gf or more / Φ5 mm SUS is preferred, and more preferably 20 gf or more / Φ5 mm SUS. On the other hand, from the viewpoint of the transferability of the electronic components to the mounting substrate, a configuration with an adhesion of 250 gf or less / Φ5 mm SUS is preferred, and more preferably 200 gf or less / Φ5 mm SUS.
[0021] In the transfer double-sided adhesive sheet of the first aspect of the present invention, the substrate preferably comprises a heat-resistant resin. This configuration is preferred from the viewpoint that when electronic components received by the transfer double-sided adhesive sheet of the first aspect of the present invention are transferred onto a mounting substrate by thermoforming, transfer defects caused by thermal expansion of the substrate can be prevented. There are no particular limitations on the heat-resistant resin, but polyimide (PI), polyethylene naphthalate (PEN), polyamide (PA), and polyetheretherketone (PEEK) are preferred.
[0022] Furthermore, a second aspect of the present invention provides a method for mounting electronic components onto a mounting substrate. The method of the second aspect of the present invention includes a step (first step) in which a first adhesive layer of a transfer double-sided adhesive sheet of the first aspect of the present invention receives a cut electronic component. In the first step, since the first adhesive layer is composed of a low-adhesion adhesive layer, it is advantageous from the perspective of reducing the force applied to the electronic component and suppressing damage to the electronic component. Additionally, it is advantageous from the perspective that when the electronic component is received in a non-contact manner by the first adhesive layer, the electronic component is easily captured by the first adhesive layer without bouncing, and can be received with good positional accuracy.
[0023] Furthermore, the method of the second aspect of the present invention includes a step (second step) of transferring the electronic component received in the first adhesive layer onto a mounting substrate. In the second step, since the first adhesive layer is composed of a low-adhesion adhesive layer, it is preferred from the viewpoint that the electronic component can be easily peeled off from the first adhesive layer when transferring the electronic component onto the mounting substrate.
[0024] In the method of the second aspect of the present invention, a semiconductor chip can be suitably used as an electronic component.
[0025] Invention Effects
[0026] For the double-sided adhesive sheet for transfer printing of the present invention, the first adhesive layer can receive multiple electronic components that have been cut into single pieces at one time without picking them up individually. In addition, the electronic components received by the first adhesive layer can be installed by transferring them onto a large-area circuit board at one time, thus significantly improving manufacturing efficiency.
[0027] Furthermore, since the first adhesive layer is preferably composed of a low-adhesion adhesive layer, it is suitable from the perspective of reducing the force applied to the electronic component and suppressing damage to the electronic component. Additionally, it is suitable from the perspective of the electronic component being easily captured by the first adhesive layer without bouncing when the electronic component is received in a non-contact manner, and being received with good positional accuracy. Moreover, since the first adhesive layer is composed of a low-adhesion adhesive layer, it is preferable from the perspective of the electronic component being easily peeled off from the first adhesive layer when transferring it onto the mounting substrate.
[0028] Furthermore, in the double-sided adhesive sheet for transfer of the present invention, since the second adhesive layer is preferably composed of a peelable adhesive layer, it is preferred from the viewpoint that the second adhesive layer can be peeled off from the carrier substrate without contamination such as glue residue, and that reworkability can be improved.
[0029] Therefore, by using the double-sided adhesive sheet for transfer of the present invention to mount electronic components onto a mounting substrate, electronic components can be mounted onto the mounting substrate with high precision and efficiency. Attached Figure Description
[0030] Figure 1 This is a cross-sectional schematic diagram illustrating one embodiment of the double-sided adhesive sheet for transfer according to the present invention.
[0031] Figure 2 This is a cross-sectional schematic diagram illustrating another embodiment of the double-sided adhesive sheet for transfer according to the present invention.
[0032] Figure 3 To indicate that it was used Figure 1 This is a cross-sectional schematic diagram of one embodiment of a mounting method for mounting electronic components onto a mounting substrate using a double-sided adhesive sheet for transfer printing.
[0033] Figure 4 To indicate that it was used Figure 1 This is a cross-sectional schematic diagram of one embodiment of the mounting method for mounting electronic components onto a mounting substrate using a double-sided adhesive sheet for transfer printing. Detailed Implementation
[0034] [Double-sided adhesive sheet for transfer printing]
[0035] The double-sided adhesive sheet for transfer printing of the present invention has a laminated structure obtained by stacking a first adhesive layer, a substrate, and a second adhesive layer in this order. Hereinafter, one embodiment of the double-sided adhesive sheet for transfer printing of the present invention will be described with reference to the accompanying drawings; however, the double-sided adhesive sheet for transfer printing of the present invention is not limited to this embodiment. Figure 1This is a cross-sectional schematic diagram illustrating one embodiment of the double-sided adhesive sheet for transfer of the present invention. 1 represents the double-sided adhesive sheet for transfer, 10 represents the substrate, 11 represents the first adhesive layer, and 12 represents the second adhesive layer.
[0036] like Figure 1 As shown, the transfer double-sided adhesive sheet 1 has a laminated structure obtained by stacking a first adhesive layer 11, a substrate 10, and a second adhesive layer 12 in this order. When mounting tiny and thin electronic components such as semiconductor chips onto a mounting substrate such as a circuit board, the first adhesive layer 11 receives the electronic components. By using the transfer double-sided adhesive sheet 1 for mounting electronic components, the first adhesive layer 11 can receive multiple electronic components that have been cut into single pieces at once, eliminating the need for individual picking. Furthermore, the electronic components received by the first adhesive layer 11 can be mounted by transferring them onto a large-area mounting substrate in one go, thus significantly improving manufacturing efficiency.
[0037] (First adhesive layer)
[0038] In the double-sided adhesive sheet for transfer printing of the present invention, the first adhesive layer is an adhesive layer for receiving and holding electronic components, and preferably includes a low-adhesion adhesive layer. From the perspective of reducing the force applied to the electronic components during reception and suppressing damage to the electronic components, the configuration of the first adhesive layer including a low-adhesion adhesive layer is suitable. Furthermore, when the first adhesive layer receives the electronic components in a non-contact manner, for example, by pushing the electronic components using a pusher member to peel them off the cutting tape and allow them to fall onto the first adhesive layer, sometimes the electronic components bounce up and cannot be received with high precision when the first adhesive layer receives the fallen electronic components. When this occurs, the positional accuracy of the electronic product decreases, and sometimes poor contact occurs. From the perspective of easily capturing the electronic components without bouncing up when the first adhesive layer receives them in a non-contact manner, and being able to receive them with good positional accuracy, the aforementioned configuration of the first adhesive layer including a low-adhesion adhesive layer is also suitable. Furthermore, it is also preferable to consider that the electronic components received by the transfer double-sided adhesive sheet can be easily peeled off from the first adhesive layer when mounting them onto the mounting substrate.
[0039] The aforementioned first adhesive layer can be made into a low-adhesion adhesive layer by adjusting the type or composition of the adhesive, the degree of crosslinking, etc.; or by combining it with a light stripping agent and a plasticizer to form a WBL (Weak Boundary Layer).
[0040] There are no particular limitations on the 180° peel adhesion of the first adhesive layer to the PET film at 25°C. However, from the viewpoint of ensuring good positional accuracy without damaging the electronic components and good transferability to the mounting substrate, a strength of 100 mN or less per 25 mm is preferred, more preferably 50 mN or less per 25 mm, and even more preferably 10 mN or less per 25 mm. Furthermore, from the viewpoint of the adhesiveness of the electronic components to the first adhesive layer, the 180° peel adhesion of the first adhesive layer to the PET film at 25°C is preferably 0.1 mN or more per 25 mm, more preferably 1 mN or more per 25 mm.
[0041] The ratio (P1b / P1a) of the first adhesive layer's 180° peel adhesion force (hereinafter, sometimes referred to as "P1b" in this specification) to the first adhesive layer's 180° peel adhesion force (hereinafter, sometimes referred to as "P1a" in this specification) to the 180° peel adhesion force (hereinafter, sometimes referred to as "P1a" in this specification) to the PET film at 25°C after holding the transfer double-sided adhesive sheet at 160°C for 5 minutes is not particularly limited, but is preferably 3 or less, more preferably 2.5 or less. From the viewpoint that the adhesion force of the first adhesive layer to the electronic component does not increase when the electronic component is transferred to the mounting substrate by heat pressing, and that it can be well peeled off and transferred to the mounting substrate, a P1b / P1a ratio of 3 or less is preferred.
[0042] Regarding the 180° peel adhesion at 25°C, the second adhesive layer of the transfer double-sided adhesive sheet is bonded to a glass plate, and a PET film is bonded to the adhesive surface of the first adhesive layer. The bonding is performed under a 2kg roller with one reciprocating press, and then aged for 30 minutes at 23°C and 50% RH. After aging, the transfer double-sided adhesive sheet is peeled off from the substrate at 25°C and 50% RH under a tensile speed of 300 mm / min and a peel angle of 180°, according to JIS Z 0237, and the 180° peel adhesion (mN / 25mm) is measured. As for the PET film, there are no particular limitations as long as it is an untreated PET film; for example, the trade name "Lumirror#25-S10, thickness 23μm" (manufactured by Toray Industries, Inc.) can be used.
[0043] The adhesive strength of the first adhesive layer can be adjusted by adjusting the type or composition of the adhesive, the degree of crosslinking, etc.; or by combining it with a light peeling agent and a plasticizer to form a WBL (weak interface layer).
[0044] In the double-sided adhesive sheet for transfer of the present invention, the storage modulus (E'1a) of the first adhesive layer at a frequency of 1 Hz and 25°C, measured using AFM-DMA, is preferably 50 MPa or less. This configuration is preferred from the viewpoint of reliably adhesively bonding the electronic component receiving the first adhesive layer. When E'1a is too high, the adhesion of the electronic component to the first adhesive layer decreases, sometimes resulting in defects such as displacement or falling of the electronic component. From the viewpoint of the adhesion of the electronic component to the first adhesive layer, E'1a is preferably 40 MPa or less, more preferably 30 MPa or less. Alternatively, it can be 20 MPa or less, or 10 MPa or less. On the other hand, from the viewpoint of transferability from the first adhesive layer to the circuit board, E'1a is preferably 0.1 MPa or more. When E'1a is too low, the adhesion of the electronic component to the first adhesive layer becomes too high, sometimes impairing the transferability when mounted on the mounting substrate. From the viewpoint of the transferability of electronic components to the mounting substrate, E'1a is preferably 0.2 MPa or more, and more preferably 0.5 MPa or more.
[0045] In the double-sided adhesive sheet for transfer of the present invention, the storage modulus (E'1b) of the first adhesive layer at a frequency of 1 kHz and 25°C, measured using AFM-DMA, is preferably 100 MPa or less. This configuration is preferred from the viewpoint that the electronic component will not bounce off the surface of the first adhesive layer when the electronic component is received in a non-contact manner, and that it can be received with good positional accuracy. When E'1b is too high, when the electronic component is dropped and received without contacting the surface of the first adhesive layer, the electronic component may bounce off the predetermined position or flip over, thereby easily reducing positional accuracy. From the viewpoint of positional accuracy of the electronic component on the first adhesive layer, E'1b is preferably 90 MPa or less, more preferably 80 MPa or less. In addition, it can be 70 MPa or less, 60 MPa or less, 50 MPa or less, 40 MPa or less, 30 MPa or less, and particularly 20 MPa or less. On the other hand, from the viewpoint of transferability from the first adhesive layer to the mounting substrate, E'1b is preferably 0.5 MPa or more. When E'1b is too low, the adhesion of the electronic component to the first adhesive layer becomes high. Furthermore, sometimes the electronic component may become embedded in the first adhesive layer when dropped, thus impairing the transferability when mounted onto the mounting substrate. From the viewpoint of transferability of the electronic component to the mounting substrate, E'1b is preferably 0.7 MPa or higher, more preferably 1 MPa or higher.
[0046] In the double-sided adhesive sheet for transfer of the present invention, the ratio (E'1b / E'1a) of the storage modulus (E'1b) of the first adhesive layer at a frequency of 1 kHz and 25°C measured using AFM-DMA to the storage modulus (E'1a) of the first adhesive layer at a frequency of 1 Hz and 25°C measured using AFM-DMA is preferably greater than 1. This configuration is preferred from the perspective of improving the balance between the adhesiveness, positional accuracy, and transferability of the electronic components on the first adhesive layer. From the viewpoint of balancing the adhesiveness, positional accuracy, and transferability of the electronic components on the mounting substrate, E'1b / E'1a is preferably 1.05 or more, more preferably 1.1 or more. There is no particular upper limit to E'1b / E'1a, but from the viewpoint of the above balance, it is preferably 3 or less.
[0047] In the double-sided adhesive sheet for transfer of the present invention, the loss modulus (E”1a) of the first adhesive layer at a frequency of 1 Hz and 25°C, measured using AFM-DMA, is preferably 7 MPa or less. This configuration is preferred from the viewpoint of excellent transferability of electronic components to the mounting substrate. If E”1a is too high, the adhesion of the electronic components to the first adhesive layer becomes too high, sometimes impairing the transferability when mounted to the mounting substrate. From the viewpoint of transferability of electronic components to the mounting substrate, E”1a is preferably 5 MPa or less, more preferably 3 MPa or less. When E”1a is too low, the adhesion of the electronic components to the first adhesive layer decreases, sometimes resulting in defects such as positional displacement or falling of the electronic components. From the viewpoint of adhesion of electronic components to the first adhesive layer, E”1a is preferably 0.01 MPa or more, more preferably 0.03 MPa or more.
[0048] The storage modulus (E'1a) at 1 Hz and 25°C, the storage modulus (E'1b) at 1 kHz and 25°C, and the loss modulus (E”1a) at 1 Hz and 25°C, as measured by AFM-DMA (atomic force microscopy (nDMA)), can be adjusted by the type or composition of the adhesive, the degree of crosslinking, etc., of the first adhesive layer mentioned above.
[0049] In the double-sided adhesive sheet for transfer of the present invention, the adhesion of the first adhesive layer to the stainless steel plate (5 mm in diameter) is preferably 10 gf / Φ5 mm SUS to 250 gf / Φ5 mm SUS. From the viewpoint of the adhesion and positional accuracy of the electronic components on the first adhesive layer, a configuration with an adhesion of 10 gf or more / Φ5 mm SUS is preferred, and more preferably 20 gf or more / Φ5 mm SUS. On the other hand, from the viewpoint of the transferability of the electronic components to the mounting substrate, a configuration with an adhesion of 250 gf or less / Φ5 mm SUS is preferred, and more preferably 200 gf or less / Φ5 mm SUS.
[0050] The adhesion of the first adhesive layer to the stainless steel plate (5mm in diameter) can be adjusted by the type or composition of the adhesive, the degree of crosslinking, and additives such as fatty acid esters or fluorinated surfactants.
[0051] In the double-sided adhesive sheet for transfer of the present invention, the surface force of the first adhesive layer is preferably -500 μN to -100 μN. From the viewpoint of the adhesion and positional accuracy of the electronic components on the first adhesive layer, a surface force of -500 μN or more is preferred, and more preferably -400 μN or more. On the other hand, from the viewpoint of the transferability of the electronic components to the mounting substrate, a surface force of -100 μN or less is preferred, and more preferably -150 μN or less.
[0052] The surface force of the first adhesive layer can be adjusted by the type or composition of the adhesive, the degree of crosslinking, and additives such as fatty acid esters or fluorinated surfactants.
[0053] In the double-sided adhesive sheet for transfer of the present invention, the arithmetic mean roughness Ra of the first adhesive layer is preferably 2 nm or less. From the viewpoint that the electronic component is easily captured by the first adhesive layer without bouncing when the electronic component is received in a non-contact manner, and can be received with good positional accuracy, the configuration of having an arithmetic mean roughness Ra of 2 nm or less is suitable. From the viewpoint that the electronic component is easily captured by the first adhesive layer without bouncing, and can be received with good positional accuracy, the arithmetic mean roughness Ra is preferably 1.8 nm or less, more preferably 1.5 nm or less, and can be 1.2 nm or less, 1 nm or less, or 0.8 nm or less. There is no particular limitation on the lower limit value of the arithmetic mean roughness Ra, but from the viewpoint of the transferability of the electronic component to the mounting substrate, it is preferably 0.1 nm or more, and can be 0.2 nm or more or 0.3 nm or more.
[0054] In the double-sided adhesive sheet for transfer of the present invention, the absolute value of the ratio of the surface force (μN) of the first adhesive layer to the arithmetic mean roughness Ra (nm) (|surface force / Ra; μN / nm|) is preferably 200 or more. From the viewpoint that the electronic component is easily captured by the first adhesive layer without bouncing when the first adhesive layer is received in a non-contact manner, and can be received with good positional accuracy, an absolute value of 200 or more is suitable. From the viewpoint that the electronic component is easily captured by the first adhesive layer without bouncing, and can be received with good positional accuracy, the absolute value of the above ratio is preferably 225 or more, more preferably 250 or more, and can be 275 or more or 300 or more. There is no particular upper limit to the absolute value of the above ratio; from the viewpoint of the transferability of the electronic component to the mounting substrate, it is preferably 550 or less, and can be 525 or less or 500 or less.
[0055] In the double-sided adhesive sheet for transfer of the present invention, the ten-point average roughness Rz of the first adhesive layer is preferably 15 nm or less. From the perspective of easily capturing the electronic component without it bouncing when the first adhesive layer is received in a non-contact manner, and achieving good positional accuracy, the configuration of having a ten-point average roughness Rz of 15 nm or less is suitable. From the perspective of easily capturing the electronic component without it bouncing, and achieving good positional accuracy, the ten-point average roughness Rz is preferably 7 nm or less, more preferably 6.8 nm or less, and can be 6.5 nm or less, 5.5 nm or less, or 5 nm or less. There is no particular limitation on the lower limit value of the ten-point average roughness Rz, but from the viewpoint of the transferability of the electronic component to the mounting substrate, it is preferably 1 nm or more, and can be 2 nm or more, or 3 nm or more.
[0056] In the double-sided adhesive sheet for transfer of the present invention, the root mean square roughness Rms of the first adhesive layer is preferably 3 nm or less. From the viewpoint that the electronic component is easily captured by the first adhesive layer without bouncing when the first adhesive layer is received in a non-contact manner, and can be received with good positional accuracy, the configuration of having a root mean square roughness Rms of 3 nm or less is suitable. From the viewpoint that the electronic component is easily captured by the first adhesive layer without bouncing, and can be received with good positional accuracy, the root mean square roughness Rms is preferably 1.5 nm or less, more preferably 1.4 nm or less, and can be 1.35 nm or less, 1.3 nm or less, or 1.2 nm or less. There is no particular limitation on the lower limit value of the root mean square roughness Rms, but from the viewpoint of the transferability of the electronic component to the mounting substrate, it is preferably 0.3 nm or more, and can be 0.4 nm or more, or 0.5 nm or more.
[0057] The surface force, arithmetic mean roughness Ra, ten-point average roughness Rz, and root mean square roughness Rms of the first adhesive layer can be measured by the method described in the embodiments described later. The arithmetic mean roughness Ra, the ratio of surface force to arithmetic mean roughness Ra, the arithmetic mean roughness Ra, the ten-point average roughness Rz, and the root mean square roughness Rms of the first adhesive layer can be adjusted by the type or composition of the adhesive, the degree of crosslinking, and additives such as fatty acid esters or fluorinated surfactants.
[0058] In the double-sided adhesive sheet for transfer of the present invention, there is no particular limitation on the thickness of the first adhesive layer, but it is preferably 1 μm or more, more preferably 3 μm or more. When the thickness is above a certain value, the first adhesive layer can easily and accurately receive electronic components, which is preferred. Furthermore, there is no particular limitation on the upper limit of the thickness of the first adhesive layer, but it is preferably 100 μm or less, more preferably 75 μm or less. When the thickness is below a certain value, it is easy and accurate to transfer electronic components onto the mounting substrate, which is preferred.
[0059] In the double-sided adhesive sheet for transfer of the present invention, there is no particular limitation on the haze of the first adhesive layer (according to JIS K7136), but it is preferably 10% or less, more preferably 5.0% or less. When the haze is 10% or less, excellent transparency can be obtained, for example, when the double-sided adhesive sheet for transfer is pasted onto the carrier substrate, the pattern on the carrier substrate (e.g., a mark indicating the transfer position of an electronic component) can be visually identified, which is preferred. It should be noted that the above-mentioned haze can be measured, for example, by forming the first adhesive layer on a spacer and letting it stand at normal temperature (23°C, 50% RH) for at least 24 hours, then peeling off the spacer, pasting the first adhesive layer onto a glass slide (e.g., a glass slide with a total transmittance of 91.8% and a haze of 0.4%), using it as a sample, and measuring it using a haze meter (manufactured by Murakami Color Technology Research Institute Co., Ltd., trade name "HM-150").
[0060] In the double-sided adhesive sheet for transfer of the present invention, there is no particular limitation on the total transmittance of the first adhesive layer in the visible light wavelength range (according to JIS K7361-1), but it is preferably 85% or more, more preferably 88% or more. When the total transmittance is 85% or more, excellent transparency can be obtained, for example, when the double-sided adhesive sheet for transfer is pasted onto the carrier substrate, the pattern on the carrier substrate (e.g., a mark indicating the transfer position of an electronic component) can be visually identified, which is preferred. It should be noted that the above-mentioned total transmittance can be measured, for example, by forming the first adhesive layer on a spacer and letting it stand at normal temperature (23°C, 50% RH) for at least 24 hours, then peeling off the spacer, pasting the first adhesive layer onto a glass slide (e.g., a glass slide with a total transmittance of 91.8% and a haze of 0.4%), using it as a sample, and measuring it using a haze meter (manufactured by Murakami Color Technology Research Institute Co., Ltd., trade name "HM-150").
[0061] There are no particular limitations on the adhesives constituting the first adhesive layer described above. Examples include silicone adhesives, urethane adhesives, acrylic adhesives, rubber adhesives, polyester adhesives, polyamide adhesives, epoxy adhesives, vinyl alkyl ether adhesives, and fluorinated adhesives. From the viewpoint of achieving good positional accuracy without damaging electronic components and good transferability onto the mounting substrate, silicone adhesives, urethane adhesives, and acrylic adhesives that are easily controlled to have low adhesion and low tack are preferred; silicone adhesives and urethane adhesives are more preferred; and silicone adhesives are even more preferred.
[0062] (Silicone adhesives)
[0063] As a silicone adhesive, there are no particular restrictions; any known or conventional silicone adhesive can be used, such as addition-type silicone adhesives, peroxide-curing silicone adhesives, and condensation-type silicone adhesives. Silicone adhesives can be either one-component or two-component. Silicone adhesives can be used alone or in combination of two or more components.
[0064] The aforementioned addition-type silicone adhesives are typically adhesives that generate silicone polymers by using a platinum compound catalyst such as chloroplatinic acid to induce an addition reaction (hydrosilylation reaction) between organopolysiloxanes having vinyl or other alkenyl groups on silicon atoms and organopolysiloxanes having hydromethoxysilyl groups. Peroxide-cured silicone adhesives are typically adhesives that generate silicone polymers by curing (crosslinking) organopolysiloxanes using peroxides. Additionally, condensation-type silicone adhesives are typically adhesives that generate silicone polymers through a dehydration or de-alcoholization reaction between polyorganosiloxanes with hydrolyzable silanyl groups such as silanol groups or alkoxysilyl groups at the ends.
[0065] As for silicone adhesives, from the viewpoint of being easy to control to have low adhesion and low tack, examples include silicone adhesive compositions containing silicone rubber and silicone resin.
[0066] As for the aforementioned silicone rubber, there are no particular restrictions on the type of organosilicon rubber component. For example, organopolysiloxanes with dimethylsiloxane, methylphenylsiloxane, etc., as the main structural units can be used. Furthermore, depending on the type of reaction, silicone rubbers with alkenyl groups bonded to silicon atoms (alkenyl-containing organopolysiloxanes; addition reaction type), silicone rubbers with at least methyl groups (peroxide curing type), and silicone rubbers with silanol groups or hydrolyzable alkoxysilyl groups at the ends (condensation type) can be used. It should be noted that the weight-average molecular weight of the organopolysiloxane in the silicone rubber is typically 150,000 or more, preferably 280,000 to 1,000,000, and particularly preferably 500,000 to 900,000.
[0067] Furthermore, as for the aforementioned silicone resin, there are no particular limitations as long as it is a silicone resin used in silicone adhesives. Examples include silicone resins containing organopolysiloxanes, where the organopolysiloxane contains a component selected from the structural unit "R3Si". 1 / 2 The M unit containing the structural unit "SiO2", the Q unit containing the structural unit "RSiO" 3 / 2The polymer (copolymer) is a polymer (polymer) of at least one unit selected from the T unit and the D unit containing the structural unit "R2SiO". It should be noted that R in the above structural unit represents a hydrocarbon group or a hydroxyl group. Examples of such hydrocarbon groups include: aliphatic hydrocarbon groups (alkyl groups such as methyl and ethyl), alicyclic hydrocarbon groups (cyclohexyl and cycloalkyl groups), and aromatic hydrocarbon groups (aryl groups such as phenyl and naphthyl). The ratio of the M unit to at least one unit selected from the Q unit, T unit, and D unit is preferably, for example, the former / the latter (molar ratio) = The concentration is approximately 0.3 / 1 to approximately 1.5 / 1 (preferably approximately 0.5 / 1 to approximately 1.3 / 1). Various functional groups, such as vinyl groups, can be introduced into the organopolysiloxane in such silicone resins as needed. It should be noted that the introduced functional groups can be those capable of undergoing cross-linking reactions. As a silicone resin, MQ resins containing M and Q units are preferred. The weight-average molecular weight of the organopolysiloxane in the silicone resin is typically 1000 or more, preferably 1000 to 20000, and particularly preferably 1500 to 10000.
[0068] There are no particular restrictions on the ratio of silicone rubber to silicone resin. From the viewpoint of easily controlling it to have low adhesion and low tack, for example, the silicone resin is preferably 100 to 220 parts by weight (especially 120 to 180 parts by weight) relative to 100 parts by weight of silicone rubber.
[0069] It should be noted that in silicone adhesive compositions containing silicone rubber and silicone resin, the silicone rubber and silicone resin can be in a mixed state where they are simply mixed, or they can react with each other to form condensates (especially partial condensates), crosslinking reaction products, addition reaction products, etc.
[0070] Furthermore, in silicone-based adhesive compositions containing silicone rubber and silicone resin, a crosslinking agent is typically included to facilitate the formation of a crosslinked structure, considering the ease of controlling low adhesion and low tack. There are no particular limitations on such crosslinking agents; siloxane-based crosslinking agents (silicone-based crosslinking agents) and peroxide-based crosslinking agents are preferred. One crosslinking agent can be used alone, or two or more can be used in combination.
[0071] As a siloxane crosslinking agent, a polyorganohydrosiloxane having two or more hydrogen atoms bonded to silicon atoms in its molecule is preferably used. In such a polyorganohydrosiloxane, in addition to hydrogen atoms, various organic groups may be bonded to the silicon atoms bonded to the hydrogen atoms. Examples of such organic groups include alkyl groups such as methyl and ethyl; aryl groups such as phenyl; and haloalkyl groups, etc. From a synthetic and processing point of view, methyl is preferred. Furthermore, the skeletal structure of the polyorganohydrosiloxane can be linear, branched, or cyclic, with a linear structure being preferred.
[0072] As peroxide-based crosslinking agents, examples include: diacyl peroxide, alkyl peroxide esters, dicarbonate peroxide, monocarbonate peroxide, ketal peroxide, dialkyl peroxide, hydroperoxide, ketone peroxide, etc. More specifically, examples include: benzoyl peroxide, tert-butyl peroxide, dicumyl peroxide, tert-butyl cumene peroxide, di-tert-butyl peroxide, 2,5-dimethyl-2,5-di-tert-butyl peroxide hexane, 2,4-dichlorobenzoyl peroxide, di-tert-butyl peroxide diisopropylbenzene, 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, 2,5-dimethyl-2,5-di-tert-butylperoxyhexyne-3, etc.
[0073] As addition-type silicone adhesives, commercially available products include those under the trade names "KR-3700", "KR-3701", "X-40-3237-1", "X-40-3240", "X-40-3291-1", and "X-40-3306" (all manufactured by Shin-Etsu Chemical Co., Ltd.). Additionally, as peroxide-curing silicone adhesives, commercially available products include those under the trade names "KR-100", "KR-101-10", and "KR-130" (all manufactured by Shin-Etsu Chemical Co., Ltd.).
[0074] The addition-type silicone adhesive composition preferably includes a curing catalyst such as a platinum catalyst. Examples of commercially available platinum catalysts include "CAT-PL-50T" (manufactured by Shin-Etsu Chemical Co., Ltd.), "DOWSIL NC-25Catalyst," or "DOWSIL SRX212Catalyst" (all manufactured by Dow Toray Industries, Ltd.). From the viewpoint of balancing the acceptability, positional accuracy, transferability to the mounting substrate, and adhesion of the electronic components in the first adhesive layer, the content of the curing catalyst is preferably about 0.1 parts by weight to about 10 parts by weight relative to 100 parts by weight of the silicone polymer (including silicone rubber, silicone resin, etc.) that is the base polymer.
[0075] (Carbamate adhesives)
[0076] There are no particular limitations on the use of urethane adhesives; known or conventional urethane adhesives can be used. From the viewpoint of easy control to achieve low adhesion and low tack, urethane adhesive compositions containing polyols, polyfunctional isocyanate compounds, and catalysts are preferred.
[0077] As for the aforementioned polyols, any suitable polyol can be used, as long as it has two or more hydroxyl groups. Examples of such polyols include: polyols with two hydroxyl groups (diols), polyols with three hydroxyl groups (triols), polyols with four hydroxyl groups (tetraols), polyols with five hydroxyl groups (pentaols), and polyols with six hydroxyl groups (hexaols). There can be only one type of polyol, or there can be two or more types.
[0078] As the aforementioned polyol, it is preferable to include a polyol with a number average molecular weight (Mn) of 400 to 20,000. Furthermore, the content percentage of polyols with a number average molecular weight (Mn) of 400 to 20,000 in the total polyol content is preferably 50% to 100% by weight, more preferably 70% to 100% by weight, even more preferably 90% to 100% by weight, particularly preferably 95% to 100% by weight, and most preferably substantially 100% by weight. By adjusting the content percentage of polyols with a number average molecular weight (Mn) of 400 to 20,000 in the polyol to the above range, for example, it is possible to provide urethane adhesives with controlled low tack and low adhesion.
[0079] Examples of the aforementioned polyols include: polyester polyols, polyether polyols, polycaprolactone polyols, polycarbonate polyols, castor oil polyols, etc.
[0080] The aforementioned polyester polyol can be obtained, for example, through an esterification reaction between the polyol component and the acid component.
[0081] Examples of the aforementioned polyol components include: ethylene glycol, diethylene glycol, 1,3-butanediol, 1,4-butanediol, neopentyl glycol, 3-methyl-1,5-pentanediol, 2-butyl-2-ethyl-1,3-propanediol, 2,4-diethyl-1,5-pentanediol, 1,2-hexanediol, 1,6-hexanediol, 1,8-octanediol, 1,9-nonanediol, 2-methyl-1,8-octanediol, 1,8-decanediol, octadecanediol, glycerin, trimethylolpropane, pentaerythritol, hexanetriol, polypropylene glycol, etc.
[0082] Examples of the aforementioned acidic components include: succinic acid, methylsuccinic acid, adipic acid, pimelic acid, azelaic acid, sebacic acid, 1,12-dodecanoic acid, 1,14-tetradecanoic acid, dimer acid, 2-methyl-1,4-cyclohexanedicarboxylic acid, 2-ethyl-1,4-cyclohexanedicarboxylic acid, terephthalic acid, isophthalic acid, phthalic acid, isophthalic acid, terephthalic acid, 1,4-naphthalenedicarboxylic acid, 4,4'-biphenyldicarboxylic acid, and their anhydrides.
[0083] Examples of the aforementioned polyether polyols include those obtained by using water, low-molecular-weight polyols (propylene glycol, ethylene glycol, glycerol, trimethylolpropane, pentaerythritol, etc.), bisphenols (bisphenol A, etc.), and dihydroxybenzenes (catechol, resorcinol, hydroquinone, etc.) as initiators to perform addition polymerization on epoxides such as ethylene oxide, propylene oxide, and butane oxide. Specifically, examples include polyethylene glycol, polypropylene glycol, and polybutane glycol.
[0084] Examples of the aforementioned polycaprolactone polyols include caprolactone-type polyester diols obtained by ring-opening polymerization of cyclic ester monomers such as ε-caprolactone and σ-valerolactone.
[0085] Examples of the aforementioned polycarbonate polyols include: polycarbonate polyols obtained by polycondensation of the aforementioned polyol components with carbonyl chloride; polycarbonate polyols obtained by transesterification condensation of the aforementioned polyol components with dimethyl carbonate, diethyl carbonate, dipropyl carbonate, diisopropyl carbonate, dibutyl carbonate, ethylbutyl carbonate, ethylene carbonate, propylene carbonate, diphenyl carbonate, dibenzyl carbonate, etc.; copolymerized polycarbonate polyols obtained by combining two or more of the aforementioned polyol components; and polycarbonate polyols obtained by esterification of the aforementioned various polycarbonate polyols with carboxyl-containing compounds. Polycarbonate polyols; polycarbonate polyols obtained by etherification of the above-mentioned polycarbonate polyols with hydroxyl-containing compounds; polycarbonate polyols obtained by transesterification of the above-mentioned polycarbonate polyols with ester compounds; polycarbonate polyols obtained by transesterification of the above-mentioned polycarbonate polyols with hydroxyl-containing compounds; polyester-type polycarbonate polyols obtained by polycondensation of the above-mentioned polycarbonate polyols with dicarboxylic acid compounds; copolymer polyether-type polycarbonate polyols obtained by copolymerization of the above-mentioned polycarbonate polyols with epoxides; etc.
[0086] Examples of castor oil polyols include those obtained by reacting castor oil fatty acids with the aforementioned polyol components. Specifically, examples include castor oil polyols obtained by reacting castor oil fatty acids with polypropylene glycol.
[0087] From the viewpoint of low adhesion, low tack, and wettability of the first adhesive layer to electronic components, a polyol having three hydroxyl groups (triol) is preferably used as an essential component. The content of the polyol having three hydroxyl groups (triol) is preferably 50% to 100% by weight, more preferably 70% to 100% by weight, relative to the total amount of components constituting the polyol.
[0088] Examples of the aforementioned polyfunctional isocyanates include aliphatic polyisocyanates, alicyclic polyisocyanates, and aromatic polyisocyanate compounds.
[0089] Examples of the aforementioned aliphatic polyisocyanates include: trimethylene diisocyanate, tetramethylene diisocyanate, hexamethylene diisocyanate, pentamethylene diisocyanate, 1,2-propylidene diisocyanate, 1,3-butylidene diisocyanate, dodecamethylene diisocyanate, and 2,4,4-trimethylhexamethylene diisocyanate.
[0090] Examples of the aforementioned alicyclic polyisocyanates include: 1,3-cyclopentene diisocyanate, 1,3-cyclohexane diisocyanate, 1,4-cyclohexane diisocyanate, isophorone diisocyanate, hydrogenated diphenylmethane diisocyanate, hydrogenated phenylenedimethylene diisocyanate, hydrogenated toluene diisocyanate, and hydrogenated tetramethylphenylenedimethylene diisocyanate.
[0091] Examples of the aforementioned aromatic polyisocyanates include: phenylene diisocyanate, 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, 2,2'-diphenylmethane diisocyanate, 4,4'-diphenylmethane diisocyanate, 4,4'-toluidine diisocyanate, 4,4'-diphenyl ether diisocyanate, 4,4'-biphenyl diisocyanate, 1,5-naphthalene diisocyanate, and phenylenediamine diisocyanate.
[0092] Among them, aliphatic polyisocyanates and their modified forms are preferred. Compared with other isocyanate crosslinking agents, aliphatic polyisocyanates and their modified forms have high flexibility in their crosslinking structure and are easy to control to achieve low adhesion and low tack. Hexamethylene diisocyanate and its modified forms are particularly preferred as aliphatic polyisocyanates and their modified forms.
[0093] For the aforementioned polyfunctional isocyanate compounds and polyols, from the viewpoint of low adhesion, low tack, and wettability of the first adhesive layer to electronic components, the equivalent ratio (NCO / OH) of the isocyanate group of the aforementioned polyfunctional isocyanate compound to the hydroxyl group of the aforementioned polyol is preferably 1 to 5, more preferably 1.1 to 3, and even more preferably 1.2 to 2.
[0094] The above-mentioned carbamate adhesive compositions preferably contain catalysts such as iron-containing compounds and / or tin-containing compounds. Specifically, examples include: tin-containing catalysts such as dibutyltin dilaurate and dioctyltin dilaurate; tri(acetylacetonate)ferric, tri(hexane-2,4-diketone)ferric, tri(heptane-2,4-diketone)ferric, tri(heptane-3,5-diketone)ferric, tri(5-methylhexane-2,4-diketone)ferric, tri(octane-2,4-diketone)ferric, tri(6-methylheptane-2,4-diketone)ferric, tri(2,6-dimethylheptane-3,5-diketone)ferric, tri(nonane-2,4-diketone)ferric, tri(nonane-4,6-diketone)ferric, tri(2,2,6,6-tetramethylheptane-3,5-diketone)ferric, tri(tetrane-6,8-diketone)ferric, tri(1-phenylene)ferric, and tri(2,2,6,6-tetramethylheptane-3,5-diketone)ferric, tri(tetrane-6,8-diketone)ferric, and tri(1-phenylene)ferric. Iron-containing catalysts include tris(hexafluoroacetylacetone) iron, tris(ethyl acetoacetate) iron, tris(n-propyl acetoacetate) iron, tris(isopropyl acetoacetate) iron, tris(n-butyl acetoacetate) iron, tris(sec-butyl acetoacetate) iron, tris(tert-butyl acetoacetate) iron, tris(methyl propionyl acetate) iron, tris(ethyl propionyl acetate) iron, tris(n-propyl propionyl acetate) iron, tris(isopropyl propionyl acetate) iron, tris(n-butyl propionyl acetate) iron, tris(sec-butyl propionyl acetate) iron, tris(tert-butyl propionyl acetate) iron, tris(benzyl acetoacetate) iron, tris(dimethyl malonate) iron, tris(diethyl malonate) iron, trimethoxy iron, triethoxy iron, triisopropoxy iron, and ferric chloride.
[0095] The amount of catalyst contained in the above-mentioned carbamate adhesive composition relative to 100 parts by weight is preferably 0.002 parts by weight to 0.5 parts by weight, more preferably 0.005 parts by weight to 0.3 parts by weight, and even more preferably 0.01 parts by weight to 0.1 parts by weight. When it is within this range, the rate of crosslinking reaction during the formation of the adhesive layer becomes faster, and the pot life of the adhesive composition also becomes longer, which is a preferred method.
[0096] Furthermore, from the viewpoint of easily controlling low adhesion and low tackiness, urethane adhesive compositions containing urethane prepolymers are preferred as urethane adhesives.
[0097] Examples of urethane adhesive compositions containing urethane prepolymers include adhesive compositions containing a polyurethane polyol as a urethane prepolymer and a polyfunctional isocyanate compound. The urethane prepolymer may be one type or two or more types. The polyfunctional isocyanate compound may be one type or two or more types.
[0098] The polyurethane polyol used as a urethane prepolymer is preferably a polyurethane polyol obtained by reacting polyester polyol and polyether polyol with an organic polyisocyanate compound in the presence of a catalyst or in the absence of a catalyst.
[0099] Any suitable polyester polyol can be used as the polyester polyol. Examples of such polyester polyols include those obtained by reacting an acidic component with a diol component. Examples of acidic components include terephthalic acid, adipic acid, azelaic acid, sebacic acid, phthalic anhydride, isophthalic acid, trimellitic acid, etc. Examples of diol components include ethylene glycol, propylene glycol, diethylene glycol, butanediol, 1,6-hexanediol, 3-methyl-1,5-pentanediol, 3,3'-dimethylolheptane, polyethylene glycol, polypropylene glycol, 1,4-butanediol, neopentyl glycol, butyl ethylpentanediol; and polyol components include glycerol, trimethylolpropane, pentaerythritol, etc. In addition, examples of polyester polyols include those obtained by ring-opening polymerization of lactones such as polycaprolactone, poly(β-methyl-γ-valerol), and polyvalerol.
[0100] The molecular weight of the polyester polyol can range from low to high. The number average molecular weight is preferably between 500 and 5000. When the number average molecular weight is less than 500, the reactivity increases, and gelation may occur easily. When the number average molecular weight is greater than 5000, the reactivity decreases, and the cohesive strength of the polyurethane polyol itself may decrease. The amount of polyester polyol used is preferably between 10 mol% and 90 mol% of the polyol constituting the polyurethane polyol.
[0101] Any suitable polyether polyol can be used as the polyether polyol. Examples of such polyether polyols include those obtained by polymerizing ethylene oxide, propylene oxide, ethylene oxide, tetrahydrofuran, and other epoxide compounds using low molecular weight polyols such as water, propylene glycol, ethylene glycol, glycerol, and trimethylolpropane as initiators. More specifically, examples of such polyether polyols include polypropylene glycol, polyethylene glycol, polybutane glycol, and other polyether polyols with two or more functional groups.
[0102] The molecular weight of the polyether polyol can range from low to high. The number average molecular weight is preferably between 1000 and 5000. When the number average molecular weight is less than 1000, the reactivity increases, and gelation may occur easily. When the number average molecular weight is greater than 5000, the reactivity decreases, and the cohesive strength of the polyurethane polyol itself may decrease. The amount of polyether polyol used is preferably between 20 mol% and 80 mol% of the polyol constituting the polyurethane polyol.
[0103] Polyether polyols can be partially replaced with diols such as ethylene glycol, 1,4-butanediol, neopentyl glycol, butyl ethyl pentanediol, glycerol, trimethylolpropane, and pentaerythritol, or polyamines such as ethylenediamine, N-aminoethyl ethanolamine, isophorone diamine, and phenylenediamine, as needed, and used in combination.
[0104] As polyether polyols, only bifunctional polyether polyols can be used, or polyether polyols with a number average molecular weight of 1000 to 5000 and having at least three hydroxyl groups per molecule can be used partially or entirely. When polyether polyols with an average molecular weight of 1000 to 5000 and having at least three hydroxyl groups per molecule are used partially or entirely, a good balance between adhesiveness and re-peelability can be achieved. For such polyether polyols, when the number average molecular weight is less than 1000, the reactivity becomes high, and gelation may be easy. In addition, for such polyether polyols, when the number average molecular weight is greater than 5000, the reactivity decreases, and the cohesiveness of the polyurethane polyol itself may decrease. A more preferred number average molecular weight for such polyether polyols is 2500 to 3500.
[0105] As an organic polyisocyanate compound, any suitable organic polyisocyanate compound can be used. Examples of such organic polyisocyanates include aromatic polyisocyanates, aliphatic polyisocyanates, aromatic aliphatic polyisocyanates, and alicyclic polyisocyanates.
[0106] Examples of aromatic polyisocyanates include: 1,3-phenylene diisocyanate, 4,4'-biphenyl diisocyanate, 1,4-phenylene diisocyanate, 4,4'-diphenylmethane diisocyanate, 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, 4,4'-toluidine diisocyanate, 2,4,6-triisocyanatotoluene, 1,3,5-triisocyanatobenzene, bianisidine diisocyanate, 4,4'-diphenyl ether diisocyanate, and 4,4',4”-triphenylmethane triisocyanate.
[0107] Examples of aliphatic polyisocyanates include: trimethylene diisocyanate, tetramethylene diisocyanate, hexamethylene diisocyanate, pentamethylene diisocyanate, 1,2-propylidene diisocyanate, 2,3-butylidene diisocyanate, 1,3-butylidene diisocyanate, dodecamethyl diisocyanate, and 2,4,4-trimethylhexamethylene diisocyanate.
[0108] Examples of aromatic aliphatic polyisocyanates include: ω,ω'-diisocyanate-1,3-dimethylbenzene, ω,ω'-diisocyanate-1,4-dimethylbenzene, ω,ω'-diisocyanate-1,4-diethylbenzene, 1,4-tetramethylphenyldimethyl diisocyanate, 1,3-tetramethylphenyldimethyl diisocyanate, etc.
[0109] Examples of alicyclic polyisocyanates include: 3-isocyanate-methyl-3,5,5-trimethylcyclohexyl isocyanate, 1,3-cyclopentane diisocyanate, 1,3-cyclohexane diisocyanate, 1,4-cyclohexane diisocyanate, methyl-2,4-cyclohexane diisocyanate, methyl-2,6-cyclohexane diisocyanate, 4,4'-methylene bis(cyclohexyl isocyanate), 1,4-bis(isocyanate-methyl)cyclohexane, 1,4-bis(isocyanate-methyl)cyclohexane, etc.
[0110] As an organic polyisocyanate compound, it can also be used in combination with trimethylolpropane adducts, biuret forms obtained by reaction with water, trimers having isocyanurate rings, etc.
[0111] As a catalyst that can be used in obtaining polyurethane polyols, any suitable catalyst can be used. Examples of such catalysts include tertiary amine compounds and organometallic compounds.
[0112] Examples of tertiary amine compounds include triethylamine, triethylenediamine, and 1,8-diazabicyclo(5.4.0)-undecene-7 (DBU).
[0113] As organometallic compounds, examples include tin-containing compounds and non-tin-containing compounds.
[0114] Examples of tin-containing compounds include: dibutyltin dichloride, dibutyltin oxide, dibutyltin dibromide, dibutyltin dimaleate, dibutyltin dilaurate (DBTDL), dibutyltin diacetate, dibutyltin sulfide, tributyltin sulfide, tributyltin oxide, tributyltin acetate, triethyltin ethoxide, tributyltin ethoxide, dioctyltin oxide, tributyltin chloride, tributyltin trichloroacetate, and tin 2-ethylhexanoate.
[0115] Examples of non-tin-containing compounds include: titanium-containing compounds such as dibutyltitanium dichloride, tetrabutyl titanate, and butoxytitanium trichloride; lead-containing compounds such as lead oleate, lead 2-ethylhexanoate, lead benzoate, and lead naphthenate; iron-containing compounds such as ferric 2-ethylhexanoate and ferric acetylacetone; cobalt-containing compounds such as cobalt benzoate and cobalt 2-ethylhexanoate; zinc-containing compounds such as zinc naphthenate and zinc 2-ethylhexanoate; zirconium-containing compounds such as zirconium naphthenate; and so on.
[0116] When using a catalyst to obtain polyurethane polyols, in systems containing both polyester polyols and polyether polyols, the different reactivity of the two catalysts can easily lead to gelation or turbidity of the reaction solution. Therefore, by using two catalysts in the process of obtaining polyurethane polyols, these problems can be easily solved by controlling the reaction rate and catalyst selectivity. Examples of such combinations of two catalysts include: tertiary amine / organometallic compounds, tin-containing / non-tin-containing compounds, and tin-containing / tin-containing compounds, preferably tin-containing / tin-containing compounds, and more preferably a combination of dibutyltin dilaurate and tin 2-ethylhexanoate. Regarding the mixing ratio, by weight, the ratio of tin 2-ethylhexanoate to dibutyltin dilaurate is preferably less than 1, more preferably 0.2 to 0.6. When the mixing ratio is 1 or more, gelation may become more likely due to the balance of catalyst activity.
[0117] When a catalyst is used to obtain polyurethane polyols, the amount of catalyst used is preferably 0.01% to 1.0% by weight relative to the total amount of polyester polyols, polyether polyols, and organic polyisocyanate compounds.
[0118] When a catalyst is used to obtain polyurethane polyols, the reaction temperature is preferably less than 100°C, more preferably 85°C to 95°C. When the temperature reaches above 100°C, it may be difficult to control the reaction rate and crosslinking structure, and it may be difficult to obtain polyurethane polyols with the specified molecular weight.
[0119] When obtaining polyurethane polyols, a catalyst may not be used. In this case, the reaction temperature is preferably 100°C or higher, more preferably 110°C or higher. Furthermore, when obtaining polyurethane polyols without a catalyst, it is preferable to allow the reaction to proceed for at least 3 hours.
[0120] Methods for obtaining polyurethane polyols include, for example, 1) adding all the polyester polyol, polyether polyol, catalyst, and organic polyisocyanate into a flask; and 2) adding the polyester polyol, polyether polyol, and catalyst into a flask and then adding the organic polyisocyanate dropwise. From the perspective of controlling the reaction, method 2) is preferred for obtaining polyurethane polyols.
[0121] In obtaining polyurethane polyols, any suitable solvent can be used. Examples of such solvents include methyl ethyl ketone, ethyl acetate, toluene, xylene, and acetone. Among these solvents, toluene is preferred.
[0122] As a polyfunctional isocyanate compound, the aforementioned polyfunctional isocyanate compounds can be cited.
[0123] As a method for manufacturing polyurethane compositions from compositions containing urethane prepolymers, any suitable manufacturing method can be adopted as long as the so-called "urethane prepolymer" is used as a raw material to manufacture polyurethane resin compositions.
[0124] (Acrylic adhesives)
[0125] There are no particular limitations on acrylic adhesives, and known or conventional acrylic adhesives can be used. For example, from the viewpoint of easy control to achieve low adhesion and low tack, acrylic adhesive compositions containing acrylic polymers as base polymers can be listed.
[0126] The aforementioned acrylic polymers are polymers that contain structural units derived from acrylic monomers (monomers having a (meth)acryloyl group in the molecule) as structural units. Preferably, the acrylic polymers contain the most structural units derived from (meth)acrylates by mass ratio. It should be noted that only one type of acrylic polymer may be used, or two or more types may be used. Furthermore, in this specification, "(meth)acrylic acid" means "acrylic acid" and / or "methacrylic acid" (any one or both of "acrylic acid" and "methacrylic acid"), and so on.
[0127] Examples of (meth)acrylates containing hydrocarbon groups include: alkyl (meth)acrylates, cycloalkyl (meth)acrylates, and aryl (meth)acrylates. Examples of alkyl (meth)acrylates include: methyl, ethyl, propyl, isopropyl, butyl, isobutyl, sec-butyl, tert-butyl, pentyl, isoamyl, hexyl, heptyl, octyl, 2-ethylhexyl, isooctyl, nonyl, decyl, isodecanyl, undecyl, dodecyl (lauryl), tridecyl, tetradecyl, hexadecyl, octadecyl, and eicosyl esters. Examples of cycloalkyl (meth)acrylates include: cyclopentyl and cyclohexyl (meth)acrylates. Examples of aryl (meth)acrylates include: phenyl and benzyl (meth)acrylates.
[0128] The aforementioned hydrocarbon-containing (meth)acrylates may be used in only one form or in two or more forms. From the viewpoint of enabling the first adhesive layer to appropriately exhibit the basic properties such as the adhesiveness of the hydrocarbon-containing (meth)acrylate, and to easily control it to have low adhesion and low tack, the proportion of hydrocarbon-containing (meth)acrylates in all monomer components used to form the acrylic polymer is preferably 40% by mass or more, more preferably 60% by mass or more.
[0129] For the purpose of improving cohesion, heat resistance, adhesion, and tack, the aforementioned acrylic polymers may contain structural units derived from other monomer components capable of copolymerizing with the aforementioned hydrocarbon-containing (meth)acrylates. Examples of these other monomer components include: carboxyl-containing monomers, acid anhydride monomers, hydroxyl-containing monomers, glycidyl-containing monomers, sulfonic acid-containing monomers, phosphate-containing monomers, acrylamide, acrylonitrile, and other functionalized monomers, as well as vinyl ester monomers. Examples of the aforementioned carboxyl-containing monomers include: acrylic acid, methacrylic acid, carboxyethyl (meth)acrylate, carboxypentyl (meth)acrylate, itaconic acid, maleic acid, fumaric acid, and crotonic acid. Examples of the aforementioned acid anhydride monomers include: maleic anhydride and itaconic anhydride. Examples of hydroxyl-containing monomers include: 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, 12-hydroxylaurate (meth)acrylate, and methyl (4-hydroxymethylcyclohexyl)methacrylate. Examples of glycidyl-containing monomers include: glycidyl (meth)acrylate and methyl glycidyl (meth)acrylate. Examples of sulfonic acid-containing monomers include: styrene sulfonic acid, allyl sulfonic acid, 2-(meth)acrylamido-2-methylpropanesulfonic acid, (meth)acrylamidopropanesulfonic acid, sulfonylpropyl (meth)acrylate, and (meth)acryloyloxynaphthalene sulfonic acid. Examples of phosphate-containing monomers include: 2-hydroxyethylacryloyl phosphate. Examples of vinyl ester monomers mentioned above include vinyl acetate, vinyl propionate, vinyl butyrate, vinyl pentanoate, vinyl cyclohexanecarboxylate, and vinyl benzoate. Only one of the aforementioned monomer components may be used, or two or more may be used. From the viewpoint of enabling the first adhesive layer to appropriately exhibit the basic properties such as the adhesiveness of (meth)acrylates containing hydrocarbon groups, and to easily control it to have low adhesion and low tack, the total percentage of the aforementioned other monomer components in all monomer components used to form the acrylic polymer is preferably 60% by mass or less, more preferably 40% by mass or less.
[0130] For the aforementioned acrylic polymers, in order to form a cross-linked structure in their polymer backbone, structural units derived from multifunctional monomers capable of copolymerizing with monomeric components that form acrylic polymers can be included. Examples of such multifunctional monomers include: hexanediol di(meth)acrylate, polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, pentaerythritol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol hexa(meth)acrylate, epoxy (meth)acrylates (e.g., polyglycidyl (meth)acrylate), polyester (meth)acrylates, urethane (meth)acrylates, and other monomers having (meth)acryloyl groups and other reactive functional groups within their molecules. Only one of the aforementioned multifunctional monomers may be used, or two or more may be used. From the viewpoint that the first adhesive layer should appropriately exhibit the basic properties such as the adhesiveness of (meth)acrylate containing hydrocarbon groups, and that it should be easy to control to have low adhesion and low tack, the ratio of the above-mentioned multifunctional monomers in all monomer components used to form acrylic polymers is preferably 40% by mass or less, more preferably 30% by mass or less.
[0131] Acrylic polymers are obtained by polymerizing one or more monomer components containing acrylic monomers. Examples of polymerization methods include solution polymerization, emulsion polymerization, bulk polymerization, and suspension polymerization.
[0132] The mass-average molecular weight of the acrylic polymer is preferably 100,000 or more, and more preferably 200,000 to 3,000,000. When the mass-average molecular weight is 100,000 or more, there is a tendency for fewer low molecular weight substances in the adhesive layer, which can further suppress contamination of electronic components, etc.
[0133] The acrylic adhesive composition forming the first adhesive layer may contain a crosslinking agent. For example, an agent capable of crosslinking the acrylic polymer can further reduce low molecular weight substances in the first adhesive layer. Furthermore, it can increase the mass-average molecular weight of the acrylic polymer, allowing for control of low adhesion and low tack. Examples of such crosslinking agents include polyisocyanate compounds, epoxy compounds, polyol compounds (polyphenolic compounds, etc.), aziridine compounds, melamine compounds, etc., with isocyanate crosslinking agents and / or epoxy crosslinking agents being preferred. When using a crosslinking agent, the amount of crosslinking agent used is preferably about 10 parts by mass or less, more preferably 0.1 parts by mass to 10 parts by mass, relative to 100 parts by mass of the acrylic polymer.
[0134] Examples of isocyanate crosslinking agents include aliphatic isocyanates, alicyclic isocyanates, and aromatic isocyanates. Examples of aliphatic isocyanates include trimethylene diisocyanate, butylene diisocyanate, hexamethylene diisocyanate, and dimer diisocyanate. Examples of alicyclic isocyanates include cyclopentylene diisocyanate, cyclohexylene diisocyanate, isophorone diisocyanate, and 1,3-bis(isocyanate-methyl)cyclohexane. Examples of aromatic isocyanates include 2,4-toluene diisocyanate, 4,4'-diphenylmethane diisocyanate, and phenylenediamine diisocyanate. In addition, other examples of isocyanate crosslinking agents include: trimethylolpropane adduct of toluene diisocyanate (trade name "Coronate L", manufactured by Tosoh Corporation) and isocyanuric acid form of hexamethylene diisocyanate (trade name "Coronate HX", manufactured by Tosoh Corporation).
[0135] Examples of epoxy crosslinking agents (multifunctional epoxy compounds) include: N,N,N',N'-tetraglycidyl-m-phenylenediamine, diglycidyl-aniline, 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane, 1,6-hexanediol diglycidyl ether, neopentyl glycol diglycidyl ether, ethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, sorbitan... Polyglycidyl ethers, glycerol polyglycidyl ethers, pentaerythritol polyglycidyl ethers, polyglycerol polyglycidyl ethers, sorbitol polyglycidyl ethers, trimethylolpropane polyglycidyl ethers, diglycidyl adipic acid ester, diglycidyl phthalate ester, tri(2-hydroxyethyl)isocyanurate triglycidyl ester, resorcinol diglycidyl ether, and bisphenol S diglycidyl ether; and epoxy resins having two or more epoxy groups within the molecule. Commercially available epoxy crosslinking agents include, for example, "Tetrad C" manufactured by Mitsubishi Gas Chemical Co., Ltd.
[0136] The adhesive composition constituting the first adhesive layer preferably contains a mild release agent. By including a mild release agent, a weak interface layer (WBL) is formed on the surface of the first adhesive layer, which can be easily controlled to achieve low adhesion and low tack.
[0137] There are no particular restrictions on the use of light stripping agents; known light stripping agents can be used without limitation, such as organosilicon stripping agents, fluorinated surfactants, fatty acid esters, etc. These substances can be used alone or in combination of two or more.
[0138] There are no particular limitations on the aforementioned silicone-based release agents; examples include thermosetting silicone-based release agents and ionizing radiation-curing silicone-based release agents. Furthermore, silicone-based release agents can be either solvent-free (without solvents) or solvent-based (dissolved or dispersed in an organic solvent). It should be noted that silicone-based release agents can be used alone or in combination of two or more.
[0139] There are no particular limitations on the aforementioned thermosetting silicone-based release agents, but release agents comprising organohydrogen polysiloxanes and organopolysiloxanes having aliphatic unsaturated groups are preferred. Furthermore, the aforementioned silicone-based release agents are preferably thermoaddition-cured silicone-based release agents that cure through crosslinking caused by a thermoaddition reaction.
[0140] As for the aforementioned thermoaddition-curable silicone-based release agents, there are no particular limitations, but preferred examples include: polysiloxanes containing Si-H groups (polysiloxanes with hydrogen atoms (H) bonded to silicon atoms (Si) in their molecules) and polysiloxanes containing Si-H-based reactive functional groups (Si-H-based reactive polysiloxanes) in their molecules. It should be noted that this release agent is cross-linked and cured through an addition reaction between the Si-H groups and the Si-H-based reactive functional groups.
[0141] In the aforementioned polysiloxanes containing Si-H groups, the Si bonded to H can be either Si in the main chain or Si in the side chain. Preferably, the aforementioned polysiloxanes containing Si-H groups are polysiloxanes containing two or more Si-H groups in the molecule. Examples of polysiloxanes containing two or more Si-H groups include dimethylhydrosiloxane polymers such as poly(dimethylsiloxane-methylsiloxane).
[0142] Furthermore, as the aforementioned Si-H-based reactive polysiloxanes, polysiloxanes in which the Si-H-based reactive functional group or a side chain containing such a functional group is bonded to the Si (e.g., Si at the end of the main chain or Si inside the main chain) of the main chain (backbone) of the siloxane polymer are preferred. Among these, polysiloxanes in which the Si-H-based reactive functional group is directly bonded to the Si in the main chain are preferred. Moreover, as the aforementioned Si-H-based reactive polysiloxanes, polysiloxanes containing two or more Si-H-based reactive functional groups in the molecule are also preferred.
[0143] Examples of Si-H reactive functional groups in the aforementioned Si-H based reactive polysiloxanes include vinyl, hexenyl, and other alkenyl groups. Examples of siloxane polymers forming the main chain portion of the aforementioned Si-H based reactive polysiloxanes include polydialkylsiloxanes such as polydimethylsiloxane, polydiethylsiloxane, and polymethylethylsiloxane (the two alkyl groups may be the same or different); polyalkylarylsiloxanes; poly(dimethylsiloxane-methylsiloxane); and polymers formed by polymerizing various Si-containing monomers. Among these, polydimethylsiloxane is preferred as the siloxane polymer forming the main chain portion.
[0144] In particular, the above-mentioned thermoaddition-curable silicone release agent is preferably a thermoaddition-curable silicone release agent containing polysiloxanes with two or more Si-H groups in the molecule and polysiloxanes with two or more Si-H reactive functional groups in the molecule.
[0145] In addition, there are no particular limitations on the above-mentioned ionizing radiation curable silicone release agents, but UV-curable silicone release agents that are cured by cross-linking reaction under ultraviolet (UV) irradiation are preferred examples.
[0146] The aforementioned UV-curable silicone-based release agents are release agents that are cured by chemical reactions such as cationic polymerization, free radical polymerization, free radical addition polymerization, and hydrosilylation under UV irradiation. Particularly preferred of the aforementioned UV-curable silicone-based release agents are UV-curable silicone-based release agents cured by cationic polymerization.
[0147] As a cationic polymeric UV-curable silicone release agent, there are no particular limitations, but preferably include: release agents comprising epoxy-containing polysiloxanes, wherein at least two epoxy groups are bonded directly or via divalent groups (methylene, ethylene, etc., alkylene groups; ethyleneoxy, propyleneoxy, etc., alkylene groups, etc.) to the Si (e.g., Si at the end of the main chain, Si inside the main chain) and / or Si contained in the side chains of the silicone polymer backbone. The bonding modes of these at least two epoxy groups to Si can be the same or different. That is, preferably include: release agents comprising polysiloxanes containing two or more epoxy-containing side chains. Examples of epoxy-containing side chains include: glycidyl groups, epoxypropoxy groups (glycidyloxy groups), 3,4-epoxycyclohexyl groups, 2,3-epoxycyclopentyl groups, etc. The epoxy-containing polysiloxane can be linear, branched, or a mixture thereof.
[0148] In particular, in the double-sided adhesive tape for transfer of the present invention, from the viewpoint of easily controlling the first adhesive layer to have low adhesion and low tack, the silicone adhesive preferably contains a thermosetting silicone release agent, and more preferably a thermoaddition reaction curable silicone release agent.
[0149] When the first adhesive layer of the transfer double-sided adhesive tape of the present invention comprises a silicone adhesive, there is no particular limitation on the content of the silicone release agent. The content of the silicone release agent is preferably 0.5 parts by weight or more and 100 parts by weight or less relative to 100 parts by weight of the silicone polymer as the base polymer. When the content is 0.5 parts by weight or more, it is easy to control the first adhesive layer to have low adhesion and low tack; more preferably, it is 1 part by weight or more, and even more preferably, it is 3 parts by weight or more. Furthermore, when the content is 100 parts by weight or less, it is easy to suppress undesirable conditions such as insufficient adhesion and difficulty in receiving electronic components; more preferably, it is 30 parts by weight or less, and even more preferably, it is 25 parts by weight or less.
[0150] By using the aforementioned fluorinated surfactant as a light stripping agent, a light stripping effect generated by the low surface free energy of the fluorinated site can be achieved.
[0151] There are no particular limitations on the aforementioned fluorinated surfactants. Examples include: fluorinated oligomers, perfluorobutane sulfonates, carboxylates containing perfluoroalkyl groups, sulfonates containing hexafluoropentane trimer derivatives, carboxylates containing hexafluoropentane trimer derivatives, quaternary ammonium salts containing hexafluoropentane trimer derivatives, betaine containing hexafluoropentane trimer derivatives, and polyoxyethylene ethers containing hexafluoropentane trimer derivatives. Among these, fluorinated oligomers are preferred. It should be noted that two or more fluorinated surfactants can be used alone or in combination.
[0152] Specific examples of the aforementioned fluorinated surfactants include, for instance, commercially available products such as: Megaface F-114 and F-410 (manufactured by DIC Corporation); Surflon S-211, S-221, S-231, S-232, S-233, S-241, S-242, S-243, and S-420 (manufactured by AGC Seimei Chemical Co., Ltd.); and Ftergent. 100, 100C, 110, 150, 150CH, 300, 310, 320, 400SW, 251, 212M, 215M, 250, 209F, 222F, 245F, 208G, 218GL, 240G, 212P, 220P, 228P, FTX-218, DFX-18 (all manufactured by NEOS Corporation), etc. These compounds can be used alone or in combination of two or more.
[0153] The weight-average molecular weight (Mw) of the aforementioned fluorinated oligomers is preferably 3,500 or more, more preferably 5,000 or more, even more preferably 10,000 or more, and particularly preferably 20,000 or more. When the weight-average molecular weight of the aforementioned fluorinated oligomers is 3,500 or more, it is easy to control for low adhesion and low tack. Furthermore, when the weight-average molecular weight is 20,000 or more, foaming during the preparation of the adhesive (composition) can be suppressed, resulting in an excellent appearance after the adhesive is applied, which is therefore preferred. In addition, the upper limit of the weight-average molecular weight (Mw) of the aforementioned fluorinated oligomers is preferably 200,000 or less, more preferably 100,000 or less. By setting the upper limit of the weight-average molecular weight (Mw) of the aforementioned fluorinated oligomers to 200,000 or less, the fluorinated oligomers are more likely to exist unevenly on the surface, making it easier to achieve a light peeling effect, which is preferred.
[0154] In addition, examples of the aforementioned fluorinated oligomers, such as commercially available products, include: Megaface F-251, F-253, F-281, F-410, F-430, F-444, F-477, F-510, F-511, F-551, F-552, F-553, F-554, F-555, F-556, F-557, F-558, F-559, F-560, F-561, F-562, F-563, F-565, F-568, F-569, F-570, F-571, and F-572 (all manufactured by DIC Corporation); Surflon S-611, S-651, and S-386 (all manufactured by AGC Seimei Chemical Co., Ltd.); Ftergent 610FM, 710FL, 710FM, 710FS, 730FL, 730LM (all manufactured by NEOS Corporation), etc. These compounds can be used alone or in combination of two or more.
[0155] When the first adhesive layer of the transfer double-sided adhesive tape of the present invention contains a fluorinated surfactant, there is no particular limitation on the content of the fluorinated surfactant. The content of the fluorinated surfactant is preferably 0.01 parts by weight or more and 5 parts by weight or less relative to 100 parts by weight of the silicone polymer as the base polymer. When the content is 0.01 parts by weight or more, it is easy to control the first adhesive layer to have low adhesion and low tack; more preferably, it is 0.05 parts by weight or more, and even more preferably, it is 0.1 parts by weight or more. Furthermore, when the content is 5 parts by weight or less, it is easy to suppress undesirable conditions such as insufficient adhesion and difficulty in receiving electronic components. From the viewpoint of suppressing reduced transparency, it is more preferably 3 parts by weight or less, and even more preferably 2 parts by weight or less.
[0156] By including fatty acid esters in the adhesive composition constituting the first adhesive layer, it is expected that the first adhesive layer will have low adhesion, low tack, and low wettability to electronic components.
[0157] Examples of the aforementioned fatty acid esters include: bisphenol A laurate of polyethylene oxide, butyl stearate, 2-ethylhexyl palmitate, 2-ethylhexyl stearate, glyceryl monobenzyl hesperidate, cetyl 2-ethylhexanoate, isopropyl myristate, isopropyl palmitate, cholesterol isostearate, lauryl methacrylate, coconut oil fatty acid methyl ester, methyl laurate, methyl oleate, methyl stearate, myristyl myristate, octyl dodecyl myristate, pentaerythritol monooleate, pentaerythritol monostearate, pentaerythritol tetrapalmitate, stearate, isotridecyl stearate, glyceryl tri(2-ethylhexanoate), butyl laurate, octyl oleate, tridecyl isononanoate, etc. There may be only one type of fatty acid ester, or there may be two or more types.
[0158] From the viewpoint of low adhesion, low tack, wettability, and contamination of the adhered object to the first adhesive layer, for example, the content of fatty acid esters contained in the above-mentioned carbamate adhesive composition is preferably 1 to 50 parts by weight, more preferably 2 to 40 parts by weight, and even more preferably 3 to 30 parts by weight, relative to 100 parts by weight of polyol.
[0159] When the adhesive composition constituting the first adhesive layer contains a light release agent, from the viewpoint of low adhesion, low tack, wettability, and contamination of the electronic components by the first adhesive layer, for example, the content (total) of the light release agent relative to 100 parts by weight of the base polymer is preferably 0.1 parts by weight or more, more preferably 1 part by weight or more, and even more preferably 3 parts by weight or more. From the viewpoint of preventing discoloration of the first adhesive layer, the content (total) of the light release agent is preferably 50 parts by weight or less, more preferably 30 parts by weight or less, and even more preferably 10 parts by weight or less.
[0160] The adhesive composition constituting the first adhesive layer preferably includes anti-deterioration agents such as antioxidants and ultraviolet absorbers. By including anti-deterioration agents, it is possible to suppress deterioration such as discoloration during storage of the double-sided adhesive sheet for transfer of the present invention, and in addition, it is possible to improve the processability such as the ease of cutting the double-sided adhesive sheet for transfer.
[0161] There are no particular limitations on the aforementioned ultraviolet absorbers. Examples include triazine ultraviolet absorbers, benzotriazole ultraviolet absorbers, benzophenone ultraviolet absorbers, hydroxybenzophenone ultraviolet absorbers, salicylate ultraviolet absorbers, and cyanoacrylate ultraviolet absorbers. These can be used alone or in combination of two or more. Among these, triazine ultraviolet absorbers and benzotriazole ultraviolet absorbers are preferred. At least one ultraviolet absorber selected from the group consisting of triazine ultraviolet absorbers having two or fewer hydroxyl groups in one molecule and benzotriazole ultraviolet absorbers having one benzotriazole skeleton in one molecule is preferred because it exhibits good solubility in the monomer used to form the acrylic adhesive composition and has high ultraviolet absorption capacity around 380 nm.
[0162] Triazine UV absorbers having two or fewer hydroxyl groups in one molecule include, specifically: 2,4-bis[{4-(4-ethylhexyloxy)-4-hydroxy}-phenyl]-6-(4-methoxyphenyl)-1,3,5-triazine (Tinosorb S, manufactured by BASF), 2,4-bis[2-hydroxy-4-butoxyphenyl]-6-(2,4-dibutoxyphenyl)-1,3,5-triazine (TINUVIN 460, manufactured by BASF), 2-(4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine-2-yl)-5-hydroxyphenyl and [(C 10 -C 16 (mainly C) 12 -C 13 The reaction product of ethylene oxide with alkoxymethyl[2,4-dimethylphenyl]-1,3,5-triazin-2-yl]-5-[3-(dodecyloxy)-2-hydroxypropoxy]phenol, the reaction product of 2-(2,4-dihydroxyphenyl)-4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine with glycidyl (2-ethylhexyl) ester (TINUVIN 405, BASF), 2-(4,6-diphenyl-1,3,5-triazin-2-yl)-5-[(hexyl)oxy]phenol (TINUVIN 1577, BASF), 2-(4,6-diphenyl-1,3,5-triazin-2-yl)-5-[2-(2-ethylhexanoyloxy)ethoxy]phenol (ADK STAB) LA46 (manufactured by ADEKA), 2-(2-hydroxy-4-[1-octoxycarbonylethoxy]phenyl)-4,6-bis(4-phenylphenyl)-1,3,5-triazine (TINUVIN 479, manufactured by BASF), etc.
[0163] In addition, examples of benzotriazole UV absorbers having one benzotriazole skeleton in one molecule include: 2-(2H-benzotriazole-2-yl)-6-(1-methyl-1-phenylethyl)-4-(1,1,3,3-tetramethylbutyl)phenol (TINUVIN 928, manufactured by BASF), 2-(2-hydroxy-5-tert-butylphenyl)-2H-benzotriazole (TINUVIN PS, manufactured by BASF), and phenylpropionic acid with 3-(2H-benzotriazole-2-yl)-5-(1,1-dimethylethyl)-4-hydroxy(C 7-9 Ester compounds of side-chain and straight-chain alkyl groups (TINUVIN 384-2, manufactured by BASF), 2-(2H-benzotriazol-2-yl)-4,6-bis(1-methyl-1-phenylethyl)phenol (TINUVIN 900, manufactured by BASF), 2-(2H-benzotriazol-2-yl)-6-(1-methyl-1-phenylethyl)-4-(1,1,3,3-tetramethylbutyl)phenol (TINUVIN 928, manufactured by BASF), the reaction product of methyl 3-(3-(2H-benzotriazol-2-yl)-5-tert-butyl-4-hydroxyphenyl)propionate / polyethylene glycol 300 (TINUVIN 1130, manufactured by BASF), 2-(2H-benzotriazol-2-yl)-p-cresol (TINUVIN... P (manufactured by BASF), 2(2H-benzotriazol-2-yl)-4,6-bis(1-methyl-1-phenylethyl)phenol (TINUVIN 234, manufactured by BASF), 2-[5-chloro(2H)-benzotriazol-2-yl]-4-methyl-6-(tert-butyl)phenol (TINUVIN 326, manufactured by BASF), 2-(2H-benzotriazol-2-yl)-4,6-di-tert-pentylphenol (TINUVIN 328, manufactured by BASF), 2-(2H-benzotriazol-2-yl)-4-(1,1,3,3-tetramethylbutyl)phenol (TINUVIN 329, manufactured by BASF), the reaction product of methyl 3-(3-(2H-benzotriazol-2-yl)-5-tert-butyl-4-hydroxyphenyl)propionate and polyethylene glycol 300 (TINUVIN 213 (manufactured by BASF), 2-(2H-benzotriazol-2-yl)-6-dodecyl-4-methylphenol (TINUVIN 571, manufactured by BASF), 2-[2-hydroxy-3-(3,4,5,6-tetrahydrophthalimidemethyl)-5-methylphenyl]benzotriazole (Sumisorb 250, manufactured by Sumitomo Chemical Co., Ltd.), etc.
[0164] In addition, examples of the aforementioned benzophenone-based ultraviolet absorbers (benzophenone compounds) and hydroxybenzophenone-based ultraviolet absorbers (hydroxybenzophenone compounds) include: 2,4-dihydroxybenzophenone, 2-hydroxy-4-methoxybenzophenone, 2-hydroxy-4-methoxybenzophenone-5-sulfonic acid (anhydrous salt and trihydrate salt), 2-hydroxy-4-octoxybenzophenone, 4-dodecyloxy-2-hydroxybenzophenone, 4-benzyloxy-2-hydroxybenzophenone, 2,2',4,4'-tetrahydroxybenzophenone, and 2,2'-dihydroxy-4,4'-dimethoxybenzophenone.
[0165] In addition, examples of salicylate-based ultraviolet absorbers (salicylate compounds) mentioned above include: phenyl 2-acryloyloxybenzoate, phenyl 2-acryloyloxy-3-methylbenzoate, phenyl 2-acryloyloxy-4-methylbenzoate, phenyl 2-acryloyloxy-5-methylbenzoate, phenyl 2-acryloyloxy-3-methoxybenzoate, phenyl 2-hydroxybenzoate, phenyl 2-hydroxy-3-methylbenzoate, phenyl 2-hydroxy-4-methylbenzoate, phenyl 2-hydroxy-5-methylbenzoate, phenyl 2-hydroxy-3-methoxybenzoate, and 2,4-di-tert-butyl-4-hydroxybenzoate (TINUVIN120, manufactured by BASF).
[0166] Examples of cyanoacrylate-based ultraviolet absorbers (cyanoacrylate compounds) include: alkyl cyanoacrylate, cycloalkyl cyanoacrylate, alkoxyalkyl cyanoacrylate, alkenyl cyanoacrylate, alkynyl cyanoacrylate, etc.
[0167] The maximum absorption wavelength of the absorption spectrum of the above-mentioned ultraviolet absorber is preferably in the wavelength range of 300 nm to 400 nm, and more preferably in the wavelength range of 320 nm to 380 nm.
[0168] Examples of antioxidants include phenolic antioxidants, phosphorus-containing antioxidants, sulfur-containing antioxidants, and amine antioxidants, with at least one selected from the latter being used. Phenolic antioxidants are preferred, and hindered phenolic antioxidants are particularly preferred.
[0169] Specific examples of phenolic antioxidants, and as monocyclic phenolic compounds, include: 2,6-di-tert-butyl-p-cresol, 2,6-di-tert-butyl-4-ethylphenol, 2,6-dicyclohexyl-4-methylphenol, 2,6-diisopropyl-4-ethylphenol, 2,6-di-tert-pentyl-4-methylphenol, 2,6-di-tert-octyl-4-n-propylphenol, 2,6-dicyclohexyl-4-n-octylphenol, 2-isopropyl-4-methyl-6-tert-butylphenol, 2-tert-butyl-4-ethyl-6-tert-octylphenol, 2-isobutyl-4-ethyl-6-tert-hexylphenol, 2-cyclohexyl-4-n-butyl-6-isopropylphenol, and styrene-modified mixed cresols. DL-α-tocopherol, stearyl β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, etc.; as bicyclic phenolic compounds, examples include: 2,2'-methylenebis(4-methyl-6-tert-butylphenol), 4,4'-butylidenebis(3-methyl-6-tert-butylphenol), 4,4'-thiobis(3-methyl-6-tert-butylphenol), 2,2'-thiobis(4-methyl-6-tert-butylphenol), 4,4'-methylenebis(2,6-di-tert-butylphenol), 2,2'-methylenebis[6-(1-methylcyclohexyl)-p-cresol], 2,2'-ethidenebis(4,6-di-tert-butylphenol), 2,2'-butylidenebis(2 3,6-dioxaoctanemethylbis[3-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionate], triethylene glycol bis[3-(3-tert-butyl-5-methyl-4-hydroxyphenyl)propionate], 1,6-hexanediol bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], 2,2'-thiodiethylenebis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], etc.; as tricyclic phenolic compounds, examples include: 1,1,3-tris(2-methyl-4-hydroxy-5-tert-butylphenyl)butane, 1,3,5-tris(2,6-dimethyl-3-hydroxy-4-tert-butylbenzyl) Examples of phenolic compounds include: 1,3,5-tris[[(3,5-di-tert-butyl-4-hydroxyphenyl)propionyloxyethyl]isocyanurate, tris(4-tert-butyl-2,6-dimethyl-3-hydroxybenzyl)isocyanurate, 1,3,5-trimethyl-2,4,6-tris(3,5-di-tert-butyl-4-hydroxybenzyl)benzene, etc.; tetracyclic phenolic compounds include: tetra[methylene-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]methane, etc.; phosphorus-containing phenolic compounds include: bis(3,5-di-tert-butyl-4-hydroxybenzylphosphonate ethyl ester)calcium, bis(3,5-di-tert-butyl-4-hydroxybenzylphosphonate ethyl ester)nickel, etc.
[0170] The aforementioned anti-deterioration agents can be used alone or in combination of two or more. From the viewpoint of inhibiting deterioration such as discoloration during storage and the processability of double-sided adhesive sheets for transfer, for example, the content of the anti-deterioration agent contained in the adhesive composition is preferably 0.01 parts by weight to 10 parts by weight, more preferably 0.03 parts by weight to 5 parts by weight, and even more preferably 0.1 parts by weight to 3 parts by weight, relative to 100 parts by weight of the adhesive composition.
[0171] The adhesive composition constituting the first adhesive layer may contain any suitable other components without impairing the effects of the present invention. Examples of such other components include, for instance: tackifiers, inorganic fillers, organic fillers, metal powders, pigments, foils, softeners, plasticizers, conductive agents, surface lubricants, leveling agents, heat stabilizers, polymerization inhibitors, lubricants, solvents, etc.
[0172] (Second adhesive layer)
[0173] In the double-sided adhesive sheet for transfer of the present invention, the second adhesive layer is an adhesive layer for temporarily fixing to the carrier substrate, and preferably includes a peelable adhesive layer. From the viewpoint of being able to peel the second adhesive layer from the carrier substrate without contamination such as glue residue, and improving reworkability, the above-mentioned configuration of the second adhesive layer including a peelable adhesive layer is preferred.
[0174] The aforementioned second adhesive layer can be made into a peelable adhesive layer by adjusting the adhesiveness through the type or composition of the adhesive, the degree of crosslinking, etc.; or by reducing the adhesive force through physical stimulation such as heat, ultraviolet light, and electromagnetic waves.
[0175] There are no particular limitations on the 180° peel adhesion of the second adhesive layer to the glass plate at 25°C. From the viewpoint of being able to peel off from the carrier substrate without contamination such as adhesive residue and improving reworkability, it is preferable to have a peel adhesion of 5000 mN or less per 25 mm, more preferably 3000 mN or less per 25 mm, and even more preferably 1000 mN or less per 25 mm. In addition, from the viewpoint of the adhesiveness of the carrier substrate on the second adhesive layer, the 180° peel adhesion of the second adhesive layer to the glass plate at 25°C is preferably 1 mN or more per 25 mm, more preferably 5 mN or more per 25 mm.
[0176] The ratio (P2b / P2a) of the peel adhesion force of the second adhesive layer to the glass plate at 25°C after holding the double-sided adhesive sheet for transfer at 160°C for 5 minutes to the peel adhesion force of the second adhesive layer to the glass plate at 25°C at 180°C (hereinafter, sometimes referred to as "P2b") is not particularly limited, but is preferably 2 or less, more preferably 2.5 or less. From the viewpoint that when electronic components received by the double-sided adhesive sheet for transfer of the present invention are transferred to the mounting substrate by heat pressing, the adhesion force of the second adhesive layer to the carrier substrate does not increase, and good peeling results in excellent reworkability, a P2b / P2a ratio of 3 or less is preferred.
[0177] The 180° peel adhesion of the second adhesive layer at 25°C can be measured in the same way as that of the first adhesive layer.
[0178] The adhesive strength of the second adhesive layer can be adjusted by adjusting the type or composition of the adhesive, the degree of crosslinking, etc., and by combining a light peeling agent and a plasticizer to form a WBL (weak interface layer).
[0179] In the double-sided adhesive sheet for transfer printing of the present invention, there is no particular limitation on the thickness of the second adhesive layer, but it is preferably 1 μm or more, and more preferably 3 μm or more. When the thickness is above a certain value, the second adhesive layer can be easily and stably fixed on the carrier substrate, which is therefore preferred. In addition, there is no particular limitation on the upper limit of the thickness of the second adhesive layer, but it is preferably 30 μm or less, and more preferably 20 μm or less. When the thickness is below a certain value, the second adhesive layer can be easily peeled off from the carrier substrate, improving reworkability, which is also preferred.
[0180] In the double-sided adhesive sheet for transfer of the present invention, there is no particular limitation on the haze of the second adhesive layer (according to JIS K7136), but it is preferably 10% or less, more preferably 5% or less. When the haze is 10% or less, excellent transparency can be obtained, for example, when the double-sided adhesive sheet for transfer is pasted onto the carrier substrate, the pattern on the carrier substrate (e.g., a mark indicating the receiving position of an electronic component) can be visually identified, which is preferred. It should be noted that the above-mentioned haze can be measured, for example, by forming the second adhesive layer on the spacer and letting it stand at normal temperature (23°C, 50% RH) for at least 24 hours, then peeling off the spacer, pasting the second adhesive layer onto a glass slide (e.g., a glass slide with a total transmittance of 91.8% and a haze of 0.4%), using it as a sample, and measuring it using a haze meter (manufactured by Murakami Color Technology Research Institute Co., Ltd., trade name "HM-150").
[0181] In the double-sided adhesive sheet for transfer of the present invention, there is no particular limitation on the total transmittance of the second adhesive layer in the visible light wavelength range (according to JIS K 7361-1), but it is preferably 85% or more, more preferably 88% or more. When the total transmittance is 85% or more, excellent transparency can be obtained, for example, when the double-sided adhesive sheet for transfer is pasted onto the carrier substrate, the pattern (e.g., a mark indicating the receiving position of an electronic component) on the carrier substrate can be visually identified, which is preferred. It should be noted that the above-mentioned total transmittance can be measured, for example, by forming the second adhesive layer on the spacer and letting it stand at normal temperature (23°C, 50% RH) for at least 24 hours, then peeling off the spacer, pasting the second adhesive layer onto a glass slide (e.g., a glass slide with a total transmittance of 91.8% and a haze of 0.4%), using it as a sample, and measuring it using a haze meter (manufactured by Murakami Color Technology Research Institute Co., Ltd., trade name "HM-150").
[0182] There are no particular limitations on the adhesives constituting the second adhesive layer described above. Examples include silicone adhesives, urethane adhesives, acrylic adhesives, rubber adhesives, polyester adhesives, polyamide adhesives, epoxy adhesives, vinyl alkyl ether adhesives, and fluorinated adhesives used in the first adhesive layer. From the viewpoint of being able to peel off from the carrier substrate without residue or other contamination, thus improving reworkability, silicone adhesives, urethane adhesives, and acrylic adhesives are preferred; urethane adhesives and acrylic adhesives are more preferred; and acrylic adhesives are even more preferred.
[0183] The second adhesive layer in the transfer double-sided adhesive sheet of the present invention can be an adhesive layer that can intentionally reduce the adhesive force through external action during the use of the transfer double-sided adhesive sheet (adhesive force reduction type adhesive layer), or an adhesive layer that does not reduce the adhesive force at all or almost completely through external action during the use of the transfer double-sided adhesive sheet (adhesive force non-reduction type adhesive layer), which can be appropriately selected according to the method, conditions, etc. of transferring electronic components using the transfer double-sided adhesive sheet of the present invention.
[0184] When the second adhesive layer is a type of adhesive layer with reduced adhesion, the manufacturing and use of the transfer double-sided adhesive sheet of the present invention can flexibly utilize the second adhesive layer to exhibit either a state of relatively high adhesion or a state of relatively low adhesion. For example, during the use of the transfer double-sided adhesive sheet of the present invention, in the process of receiving electronic components on the first adhesive layer, utilizing the state of relatively high adhesion of the second adhesive layer can suppress and prevent the transfer double-sided adhesive sheet from lifting off the carrier substrate. On the other hand, subsequently, during the process of peeling the transfer double-sided adhesive sheet of the present invention off the carrier substrate, reducing the adhesion of the second adhesive layer can improve reworkability.
[0185] Examples of adhesives that can form such a layer of adhesive with reduced adhesion include radiation-curing adhesives and heat-foaming adhesives. One type of adhesive or two or more types of adhesives can be used to form this layer.
[0186] As for the aforementioned radiation-curing adhesives, adhesives that can be cured by irradiation with electron beams, ultraviolet rays, alpha rays, beta rays, gamma rays, or X-rays can be used, and adhesives that can be cured by ultraviolet irradiation (ultraviolet-curing adhesives) are particularly preferred.
[0187] Examples of radiation-curing adhesives include additive-type radiation-curing adhesives containing a base polymer such as acrylic polymers and a radiation-polymerizable monomer or oligomer component with functional groups such as carbon-carbon double bonds that are radiation-polymerizable.
[0188] As the base polymer, an acrylic polymer, the same as that used in the first adhesive layer, can be used. From the viewpoint of enabling the second adhesive layer to appropriately exhibit the basic properties such as the adhesiveness of (meth)acrylate containing hydrocarbon groups, and of easily controlling adhesion and peelability, the proportion of (meth)acrylate containing hydrocarbon groups in all monomer components used to form the acrylic polymer is preferably 40% by mass or more, more preferably 60% by mass or more.
[0189] The aforementioned acrylic polymers may contain hydroxyl-containing monomers. When the acrylic polymer in the second adhesive layer contains hydroxyl-containing monomers, the second adhesive layer readily achieves moderate cohesiveness. From the viewpoint of achieving moderate adhesiveness and cohesiveness in the second adhesive layer, the ratio of hydroxyl-containing monomers in the aforementioned acrylic polymer is, for example, 0.1% to 30% by mass, preferably 0.5% to 20% by mass.
[0190] The aforementioned acrylic polymers may contain carboxyl-containing monomers. When the acrylic polymer in the second adhesive layer contains carboxyl-containing monomers, the second adhesive layer readily achieves moderate adhesive reliability. From the viewpoint of achieving moderate adhesive reliability in the second adhesive layer, the ratio of carboxyl-containing monomers in the aforementioned acrylic polymer is, for example, 0.1% to 30% by mass, preferably 0.5% to 20% by mass.
[0191] The aforementioned acrylic polymers may contain vinyl ester monomers. When the acrylic polymer within the second adhesive layer contains vinyl ester monomers, the second adhesive layer readily achieves moderate cohesiveness. From the viewpoint of achieving moderate cohesiveness in the second adhesive layer, the ratio of vinyl ester monomers in the aforementioned acrylic polymer is, for example, 0.1% to 60% by mass, preferably 0.5% to 50% by mass.
[0192] The acrylic adhesive composition forming the second adhesive layer may contain a crosslinking agent. For example, an agent capable of crosslinking the acrylic polymer can further reduce low molecular weight substances in the second adhesive layer. Additionally, it can increase the weight-average molecular weight of the acrylic polymer, allowing for control of low adhesion and peel strength. Examples of such crosslinking agents include polyisocyanate compounds, epoxy compounds, polyol compounds (polyphenolic compounds, etc.), aziridine compounds, melamine compounds, etc., with isocyanate crosslinking agents and / or epoxy crosslinking agents being preferred. When using a crosslinking agent, the amount of crosslinking agent used is preferably about 10 parts by weight or less, more preferably 0.1 parts by weight to 10 parts by weight, relative to 100 parts by weight of the acrylic polymer.
[0193] The acrylic adhesive composition forming the second adhesive layer can use a crosslinking accelerator. The type of crosslinking accelerator can be appropriately selected depending on the type of crosslinking agent used. It should be noted that, in this specification, a crosslinking accelerator refers to a catalyst that increases the rate of the crosslinking reaction using the crosslinking agent. Examples of such crosslinking accelerators include: tin (Sn)-containing compounds such as dioctyltin dilaurate, dibutyltin dilaurate, dibutyltin diacetate, dibutyltin diacetylacetone, tetra-n-butyltin, and trimethyltin hydroxide; N-containing compounds such as amines and imidazoles such as N,N,N',N'-tetramethylhexanediamine and triethylamine; etc. Among these, Sn-containing compounds are preferred. The use of these crosslinking accelerators is particularly effective when using a hydroxyl-containing monomer as the aforementioned minor monomer and an isocyanate-based crosslinking agent as the crosslinking agent. The amount of crosslinking accelerator contained in the adhesive composition, relative to 100 parts by weight of the above acrylic polymer, can be set to, for example, about 0.001 parts by weight to about 0.5 parts by weight (preferably about 0.001 parts by weight to about 0.1 parts by weight).
[0194] Examples of the aforementioned radiation-polymerizable monomer components include: urethane (meth)acrylate, trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol monohydroxypenta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, and 1,4-butanediol di(meth)acrylate. Examples of the aforementioned radiation-polymerizable oligomer components include: various oligomers such as polyurethanes, polyethers, polyesters, polycarbonates, and polybutadienes, preferably oligomers with a molecular weight of about 100 to about 30,000. The content of the aforementioned radiation-curable monomer and oligomer components in the radiation-curable adhesive forming the second adhesive layer is, for example, about 5 parts by mass to about 500 parts by mass, preferably about 40 parts by mass to about 150 parts by mass, relative to 100 parts by mass of the aforementioned base polymer. Alternatively, as an additive-type radiation-curing adhesive, the radiation-curing adhesive disclosed in Japanese Patent Application Publication No. 60-196956 can be used, for example.
[0195] As an example of the aforementioned radiation-curing adhesive, an intrinsic radiation-curing adhesive can also be cited: a base polymer containing functional groups such as carbon-carbon double bonds with radiation-polymerizable properties in the polymer side chains, polymer backbone, and polymer backbone ends. When such an intrinsic radiation-curing adhesive is used, there is a tendency to suppress unexpected changes in adhesive properties over time caused by the migration of low molecular weight components within the formed second adhesive layer.
[0196] Acrylic polymers are preferred as the base polymer contained in the aforementioned intrinsic radiation-curing adhesives. As a method for introducing radiation-polymerizable carbon-carbon double bonds into acrylic polymers, one possible method is to polymerize (copolymerize) a raw material monomer containing a monomer component having a first functional group to obtain an acrylic polymer, and then subject a compound having a second functional group capable of reacting with the aforementioned first functional group and radiation-polymerizable carbon-carbon double bonds to a condensation or addition reaction with the acrylic polymer while maintaining the radiation-polymerizable nature of the carbon-carbon double bonds.
[0197] Examples of combinations of the first and second functional groups mentioned above include: carboxyl and epoxy groups, epoxy and carboxyl groups, carboxyl and aziridinyl groups, aziridinyl and carboxyl groups, hydroxyl and isocyanate groups, and isocyanate and hydroxyl groups. From the viewpoint of easy reaction tracking, combinations of hydroxyl and isocyanate groups, and combinations of isocyanate and hydroxyl groups are preferred. From the viewpoint that while the production of polymers with highly reactive isocyanate groups is technically challenging, it is easy to produce and obtain acrylic polymers with hydroxyl groups. Examples of isocyanate compounds containing unsaturated functional groups and possessing isocyanate groups and radiation-polymerizable carbon-carbon double bonds include: methacryloyl isocyanate, 2-methacryloyloxyethyl isocyanate, and m-isopropenyl-α,α-dimethylbenzyl isocyanate. In addition, examples of acrylic polymers containing hydroxyl groups include polymers that contain structural units derived from ether compounds such as the aforementioned hydroxyl-containing monomers, 2-hydroxyethyl vinyl ether, 4-hydroxybutyl vinyl ether, and diethylene glycol monovinyl ether.
[0198] The aforementioned radiation-curing adhesive preferably contains a photopolymerization initiator. Examples of such photopolymerization initiators include: α-keto alcohols, acetophenones, benzoin ethers, ketals, aromatic sulfonyl chlorides, photoactive oximes, benzophenones, thioxanones, camphorquinones, haloketones, phosphine oxides, and acylphosphonates. Examples of such α-keto alcohols include: 4-(2-hydroxyethoxy)phenyl(2-hydroxy-2-propyl) methyl ketone, α-hydroxy-α,α'-dimethylacetophenone, 2-methyl-2-hydroxyacetophenone, and 1-hydroxycyclohexylphenyl methyl ketone. Examples of such acetophenones include: methoxyacetophenone, 2,2-dimethoxy-2-phenylacetophenone, 2,2-diethoxyacetophenone, and 2-methyl-1-[4-(methylthio)-phenyl]-2-morpholinopropane-1-one. Examples of the aforementioned benzoin ether compounds include, for example, benzoin ethyl ether, benzoin isopropyl ether, and anisolein methyl ether. Examples of the aforementioned ketal compounds include, for example, benzoin dimethyl ketal. Examples of the aforementioned aromatic sulfonyl chloride compounds include, for example, 2-naphthalenesulfonyl chloride. Examples of the aforementioned photoactive oxime compounds include, for example, 1-phenyl-1,2-propanedione-2-(O-ethoxycarbonyl)oxime. Examples of the aforementioned benzophenone compounds include, for example, benzophenone, benzoylbenzoic acid, and 3,3'-dimethyl-4-methoxybenzophenone. Examples of the aforementioned thioxanthone compounds include, for example, thioxanthone, 2-chlorothioxanthone, 2-methylthioxanthone, 2,4-dimethylthioxanthone, isopropylthioxanthone, 2,4-dichlorothioxanthone, 2,4-diethylthioxanthone, and 2,4-diisopropylthioxanthone. The content of photopolymerization initiator in the radiation-curable adhesive is, for example, 0.05 to 20 parts by mass relative to 100 parts by mass of the base polymer.
[0199] The aforementioned heat-expanding adhesives contain components that foam and expand upon heating (foaming agents, thermally expandable microspheres, etc.). Various inorganic and organic foaming agents can be listed as examples of such foaming agents. Examples of inorganic foaming agents include: ammonium carbonate, ammonium bicarbonate, sodium bicarbonate, ammonium nitrite, sodium borohydride, and azide compounds. Examples of organic foaming agents include: chlorofluoroalkane such as trichlorofluoromethane and dichlorofluoromethane; azo compounds such as azobisisobutyronitrile, azodicarbonamide, and barium azodicarbonate; hydrazine compounds such as p-toluenesulfonyl hydrazine, diphenyl sulfone-3,3'-disulfonyl hydrazine, 4,4'-oxobis(benzenesulfonyl hydrazine), and allylbis(sulfonyl hydrazine); aminourea compounds such as p-toluenesulfonamide and 4,4'-oxobis(benzenesulfonamide); triazole compounds such as 5-morpholino-1,2,3,4-thiatriazole; and N-nitroso compounds such as N,N'-dinitrospentamethylenetetramine and N,N'-dimethyl-N,N'-dinitrosterephthalamide. Examples of thermally expandable microspheres include microspheres composed of a substance that easily vaporizes and expands upon heating, encapsulated within the shell. Examples of substances that easily vaporize and expand upon heating include isobutane, propane, and pentane. Thermally expandable microspheres can be produced by encapsulating these substances within a shell-forming material using methods such as condensation or interfacial polymerization. The shell-forming material can be composed of substances exhibiting thermal melting properties or substances capable of rupture through the thermal expansion of the encapsulated material. Examples of such substances include vinylidene chloride-acrylonitrile copolymer, polyvinyl alcohol, polyvinyl butyral, polymethyl methacrylate, polyacrylonitrile, polyvinylidene chloride, and polysulfone.
[0200] As an example of an adhesive layer that does not reduce adhesion, a pressure-sensitive adhesive layer can be cited. It should be noted that a pressure-sensitive adhesive layer includes an adhesive layer that has been cured by prior radiation irradiation using an adhesive layer formed from a radiation-curing adhesive, as described above, which is an adhesive layer with reduced adhesion, but which possesses a certain degree of adhesion. As the adhesive forming the adhesive layer that does not reduce adhesion, one adhesive or two or more adhesives can be used. Furthermore, the second adhesive layer may be entirely an adhesive layer that does not reduce adhesion, or a portion of the second adhesive layer may be an adhesive layer that does not reduce adhesion. For example, when the second adhesive layer has a single-layer structure, the entire second adhesive layer may be an adhesive layer that does not reduce adhesion, or a specific portion of the second adhesive layer may be an adhesive layer that does not reduce adhesion, while other portions may be adhesive layers that reduce adhesion. Furthermore, when the second adhesive layer has a laminated structure, all adhesive layers in the laminated structure may be adhesive layers that do not reduce adhesion, or a portion of the adhesive layers in the laminated structure may be adhesive layers that do not reduce adhesion.
[0201] For an adhesive layer that has been cured by prior radiation irradiation (a radiation-cured adhesive layer after radiation irradiation) formed from a radiation-curable adhesive, even if the adhesive strength is reduced due to radiation irradiation, it still exhibits the adhesiveness produced by the contained polymer components, and can exert the minimum adhesive strength required for the transfer double-sided adhesive sheet of the present invention. When using a radiation-cured adhesive layer after radiation irradiation, in the surface extension direction of the second adhesive layer, the entire second adhesive layer may be a radiation-cured adhesive layer after radiation irradiation, or a portion of the second adhesive layer may be a radiation-cured adhesive layer after radiation irradiation, and the remaining portion may be a radiation-cured adhesive layer without radiation irradiation. It should be noted that, in this specification, "radiation-cured adhesive layer" refers to an adhesive layer formed from a radiation-curable adhesive, including both a radiation-curable adhesive layer without radiation irradiation and a radiation-cured adhesive layer after radiation irradiation where the adhesive layer has been cured by radiation irradiation.
[0202] As the adhesive forming the aforementioned pressure-sensitive adhesive layer, known or conventional pressure-sensitive adhesives can be used, and acrylic adhesives with acrylic polymers as the base polymer are preferred. When the second adhesive layer contains an acrylic polymer as the pressure-sensitive adhesive, this acrylic polymer is preferably a polymer containing structural units derived from (meth)acrylates as the most abundant structural units by mass ratio. As the aforementioned acrylic polymer, for example, acrylic polymers described as those that can be included in the aforementioned additive-type radiation-curing adhesives can be used.
[0203] (Substrate)
[0204] The substrate in the double-sided adhesive sheet for transfer printing of the present invention functions as a support in the first adhesive layer and the second adhesive layer. Examples of substrates include plastic substrates (especially plastic films). The substrate can be a single layer or a laminate of the same or different types of substrates.
[0205] Examples of resins constituting the aforementioned plastic substrates include: low-density polyethylene, linear low-density polyethylene, medium-density polyethylene, high-density polyethylene, ultra-low-density polyethylene, random copolymer polypropylene, block copolymer polypropylene, homopolymer polypropylene, polybutene, polymethylpentene, ethylene-vinyl acetate copolymer (EVA), ionomers, ethylene-(meth)acrylic acid copolymer, ethylene-(meth)acrylic acid (random, alternating) copolymer, ethylene-butene copolymer, ethylene-hexene copolymer, and other polyolefin resins; polyurethane; polyesters such as polyethylene terephthalate (PET), polyethylene naphthalate, and polybutylene terephthalate (PBT); polycarbonate; polyimide; polyetheretherketone; polyetherimide; polyamides such as aromatic polyamides and fully aromatic polyamides; polyphenylene sulfide; fluorinated resins; polyvinyl chloride; polyvinylidene chloride; cellulose resins; and silicone resins. From the viewpoint that electronic components received by the double-sided adhesive sheet of the present invention are transferred to a mounting substrate by heat pressing (e.g., 150°C) and mounted, exhibiting good heat resistance, minimal expansion and contraction due to heat, and enabling high-precision mounting, the substrate preferably contains heat-resistant resins such as polyimide (PI), polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polyamide (PA), and polyetheretherketone (PEEK) as its main component, and more preferably polyimide as its main component. It should be noted that the main component of the substrate refers to the component that accounts for the largest mass percentage in the constituent components. Only one of the above-mentioned resins may be used, or two or more may be used. In the case where the second adhesive layer is a radiation-cured adhesive layer as described above, the substrate preferably has radiometric transmittance.
[0206] When the substrate is a plastic film, the plastic film can be unoriented or oriented in at least one direction (uniaxial direction, biaxial direction, etc.), but unoriented films are less likely to exhibit heat shrinkage and are therefore preferred.
[0207] To improve adhesion and retention with the adhesive layer, the surfaces of the substrate on the first and / or second adhesive layer side may undergo physical treatments such as corona discharge treatment, plasma treatment, sandblasting, ozone exposure treatment, flame exposure treatment, high-voltage electric shock exposure treatment, and ionizing radiation treatment; chemical treatments such as chromic acid treatment; coating agents (primers); and easy-to-adhere treatments using silicone primers. Furthermore, to impart antistatic properties, in addition to forming a conductive vapor-deposited layer containing metals, alloys, or their oxides on the substrate surface, a conductive polymer such as PEDOT-PSS may be coated. Preferably, the entire surface of the substrate on the adhesive layer side undergoes a surface treatment to improve adhesion.
[0208] From the viewpoint of ensuring the strength of the substrate to function as a support in the transfer double-sided adhesive sheet of the present invention, the thickness of the substrate is preferably 5 μm or more, more preferably 10 μm or more, further preferably 15 μm or more, and particularly preferably 20 μm or more. Furthermore, from the viewpoint of achieving appropriate flexibility in the transfer double-sided adhesive sheet of the present invention, the thickness of the substrate is preferably 200 μm or less, more preferably 180 μm or less, and further preferably 150 μm or less.
[0209] In the double-sided adhesive sheet for transfer printing of the present invention, there is no particular limitation on the haze of the substrate (according to JIS K7136), but it is preferably 10% or less, more preferably 5.0% or less. When the haze is 10% or less, excellent transparency can be obtained, for example, when the double-sided adhesive sheet for transfer printing is pasted onto the carrier substrate, the pattern (e.g., a mark indicating the receiving position of an electronic component) on the carrier substrate can be visually identified, which is preferred. It should be noted that the above-mentioned haze can be measured using a haze meter (manufactured by Murakami Color Technology Research Institute Co., Ltd., trade name "HM-150").
[0210] In the double-sided adhesive sheet for transfer printing of the present invention, there is no particular limitation on the total transmittance of the substrate in the visible light wavelength range (according to JIS K 7361-1), but it is preferably 85% or more, more preferably 88% or more. When the total transmittance is 85% or more, excellent transparency can be obtained, for example, when the double-sided adhesive sheet for transfer printing is pasted onto the carrier substrate, the pattern (e.g., a mark indicating the receiving position of an electronic component) on the carrier substrate can be visually identified, which is preferred. It should be noted that the above-mentioned total transmittance can be measured using a haze meter (manufactured by Murakami Color Technology Research Institute Co., Ltd., trade name "HM-150").
[0211] (spacer)
[0212] The adhesive layer surface (the bonding surface of the first adhesive layer and / or the second adhesive layer) of the double-sided adhesive sheet for transfer of the present invention can be protected by a spacer until use. The spacer serves as a protective material for the adhesive layer and is peeled off when the adhesive sheet is adhered to the substrate. Figure 2 This is a cross-sectional schematic diagram illustrating one embodiment of the double-sided adhesive sheet for transfer according to the present invention. 1 represents the double-sided adhesive sheet for transfer, 10 represents the substrate, 11 represents the first adhesive layer, 12 represents the second adhesive layer, and 110 and 120 represent spacers. It should be noted that spacers are not necessarily required.
[0213] As the aforementioned spacer, conventional release paper or the like can be used. Specifically, for example, a substrate having a release-treated layer obtained by a release agent on at least one surface can be used; and a low-adhesion substrate containing fluoropolymers (e.g., polytetrafluoroethylene, polychlorotrifluoroethylene, polyvinylidene fluoride, polyvinylidene fluoride, tetrafluoroethylene-hexafluoropropylene copolymer, chlorofluoroethylene-vinylidene fluoride copolymer, etc.) or a low-adhesion substrate containing non-polar polymers (e.g., olefin resins such as polyethylene and polypropylene).
[0214] As the aforementioned spacer, it is preferable to use a spacer on at least one surface of the spacer substrate having a release layer formed thereon. Examples of such spacer substrates include: polyester film (polyethylene terephthalate film, etc.), olefin resin film (polyethylene film, polypropylene film, etc.), polyvinyl chloride film, polyimide film, polyamide film (nylon film), rayon film, and other plastic substrate films (synthetic resin films); paper (high-grade paper, Japanese paper, kraft paper, cellophane, synthetic paper, surface-coated paper, etc.); and substrates obtained by multiplying them through lamination, co-extrusion, etc. (2- to 3-layer composites), etc.
[0215] There are no particular limitations on the release agent used to form the aforementioned release treatment layer; for example, silicone-based release agents, fluorinated release agents, long-chain alkyl-based release agents, etc., can be used. Two or more release agents can be used alone or in combination.
[0216] It should be noted that, since the first adhesive layer is composed of a low-adhesion adhesive layer, substrates that have not been treated with a release agent can also be used as spacers.
[0217] To prevent adverse effects on electronic components, the aforementioned spacer may have an antistatic layer formed on at least one side of the spacer substrate. The antistatic layer may be formed on one side of the spacer (the peeled-off side or the untreated side) or on both sides of the spacer (the peeled-off side and the untreated side).
[0218] Examples of antistatic agents contained in the antistatic resin that forms the above-mentioned antistatic layer include: quaternary ammonium salts and pyridine. The compounds include: salts; cationic antistatic agents with cationic functional groups such as primary, secondary, and tertiary amine groups; anionic antistatic agents with anionic functional groups such as sulfonates, sulfates, phosphonates, and phosphates; zwitterionic antistatic agents such as alkyl betaines and their derivatives, imidazolines and their derivatives, and alanine and its derivatives; nonionic antistatic agents such as amino alcohols and their derivatives, glycerol and its derivatives, and polyethylene glycol and its derivatives; and ionically conductive polymers obtained by polymerizing or copolymerizing the above-mentioned cationic, anionic, and zwitterionic monomers with ionically conductive groups. These compounds can be used alone or in combination of two or more.
[0219] There are no particular restrictions on the thickness of the spacer; it can be appropriately selected from the range of 5μm to 100μm.
[0220] The manufacturing method of the double-sided adhesive sheet for transfer of the present invention varies depending on the composition of the adhesive composition described above, and is not particularly limited. Known forming methods can be used, such as the following methods (1) to (4).
[0221] (1) A method of manufacturing an adhesive sheet by coating (applying) the above-mentioned adhesive composition onto a substrate to form a composition layer and curing the composition layer (e.g., by heat curing or by irradiation with active energy rays such as ultraviolet light) to form an adhesive layer.
[0222] (2) A method of manufacturing an adhesive sheet by coating the adhesive composition described above onto a spacer to form a composition layer, curing the composition layer (e.g., by heat curing or curing by irradiation with active energy rays such as ultraviolet light) to form an adhesive layer, and then transferring the adhesive layer onto a substrate.
[0223] (3) A method of manufacturing an adhesive sheet by applying (coating) the above adhesive composition onto a substrate and drying it to form an adhesive layer.
[0224] (4) A method of manufacturing an adhesive sheet by coating (applying) the above adhesive composition onto a spacer and drying it to form an adhesive layer, and then transferring the adhesive layer onto a substrate.
[0225] From the viewpoint of excellent productivity and the ability to form a uniform and smooth adhesive layer, the heat curing method is preferred as the curing method in (1) to (4) above.
[0226] As a method for applying (coating) the above-mentioned adhesive composition to a specified surface, any known coating method can be used without particular limitation. Examples include: roller coating, roller licking coating, gravure coating, reverse coating, roller brush coating, spraying, dip roller coating, doctor blade coating, doctor blade coating, air knife coating, curtain coating, lip die coating, and extrusion coating using a die coating machine, etc.
[0227] There is no particular limitation on the thickness (total thickness) of the double-sided adhesive sheet for transfer printing according to the present invention, but it is preferably 10 μm or more, more preferably 15 μm or more. When the thickness is above a certain value, the first adhesive layer can easily and accurately receive electronic components, which is preferred. Furthermore, there is no particular limitation on the upper limit of the thickness (total thickness) of the double-sided adhesive sheet for transfer printing according to the present invention, but it is preferably 500 μm or less, more preferably 300 μm or less. When the thickness is below a certain value, it is easy and accurate to transfer electronic components onto the mounting substrate, which is preferred. It should be noted that the thickness of the spacer is not included in the thickness of the double-sided adhesive sheet for transfer printing according to the present invention.
[0228] The haze (according to JIS K7136) of the double-sided adhesive sheet for transfer of the present invention is not particularly limited, but is preferably 10% or less, more preferably 5.0% or less. When the haze is 10% or less, excellent transparency can be obtained, for example, the pattern (e.g., a mark indicating the receiving position of an electronic component) on the carrier substrate can be visually identified when the double-sided adhesive sheet for transfer is pasted onto the carrier substrate, which is preferred. It should be noted that the above-mentioned haze can be measured, for example, by leaving the double-sided adhesive sheet for transfer at normal temperature (23°C, 50% RH) for at least 24 hours, then peeling off the spacer with the spacer in place, pasting the double-sided adhesive sheet for transfer onto a glass slide (e.g., a glass slide with a total transmittance of 91.8% and a haze of 0.4%), using it as a sample, and measuring it using a haze meter (manufactured by Murakami Color Technology Research Institute Co., Ltd., trade name "HM-150").
[0229] There are no particular limitations on the total transmittance (according to JIS K7361-1) of the transfer double-sided adhesive sheet of the present invention in the visible light wavelength range, but it is preferably 85% or more, more preferably 88% or more. When the total transmittance is 85% or more, excellent transparency can be obtained, for example, when the transfer double-sided adhesive sheet is pasted on the carrier substrate, the pattern (e.g., a mark indicating the receiving position of an electronic component) on the carrier substrate can be visually identified, which is preferred. It should be noted that the above-mentioned total transmittance can be measured, for example, by leaving the transfer double-sided adhesive sheet at normal temperature (23°C, 50% RH) for at least 24 hours, then peeling off the spacer with the spacer in place, pasting the transfer double-sided adhesive sheet onto a glass slide (e.g., a glass slide with a total transmittance of 91.8% and a haze of 0.4%), using it as a sample, and measuring it using a haze meter (manufactured by Murakami Color Technology Research Institute Co., Ltd., trade name "HM-150").
[0230] The double-sided adhesive sheet for transfer printing of the present invention can be suitably used in methods for mounting electronic components onto a mounting substrate. The method for mounting electronic components onto a mounting substrate using the double-sided adhesive sheet for transfer printing of the present invention preferably includes the following steps.
[0231] The process of receiving the cut electronic components in the first adhesive layer of the double-sided adhesive sheet for transfer according to the present invention (first process).
[0232] The process of transferring the electronic components received by the first adhesive layer onto the mounting substrate (second process).
[0233] Figure 3 This is a cross-sectional schematic diagram illustrating an embodiment of the first step in a method for mounting electronic components onto a mounting substrate using the transfer double-sided adhesive sheet of the present invention.
[0234] exist Figure 3 In (a), the double-sided adhesive sheet 1 for transfer is adhered to the carrier substrate 22 using the adhesive side of the second adhesive layer 12. Marking patterns for arranging electronic components may be present on the surface of the carrier substrate 22 that is adhered to the second adhesive layer 12. Because the double-sided adhesive sheet 1 for transfer has high transparency, the marking patterns on the carrier substrate 22 can be visually identified.
[0235] Multiple electronic components 21, which are made into single pieces by cutting, are disposed on the upper part of the adhesive surface of the first adhesive layer 11, opposite to and separated from the adhesive surface of the first adhesive layer 11, while being pasted on the cutting tape 20.
[0236] exist Figure 3In (b), the ejector pin 23 pushes the electronic component 21 from the unattached side of the cutting tape 20, bringing the electronic component 21 close to the adhesive surface of the first adhesive layer 11, where the adhesive surface of the first adhesive layer 11 receives the electronic component 21. Receiving can be done by bringing the electronic component 21 into contact with the first adhesive layer 11, or it can be done non-contactly. In the case of non-contact receiving, the electronic component 21 is pushed until it peels off the cutting tape 20, causing it to fall onto the adhesive surface. When receiving by bringing it into contact, the adhesive surface of the first adhesive layer 11 has low adhesion, resulting in weak stress when receiving the electronic component 21, thus suppressing damage to the electronic component 21. In the case of non-contact receiving, the adhesive surface of the first adhesive layer 11 has low adhesion, allowing for accurate positioning of the falling electronic component 21. It should be noted that the electronic component 21 can also be peeled off the cutting tape 20 by irradiating it with ultraviolet light, a laser beam, or other radiation instead of the ejector pin 23.
[0237] The electronic components 21 can be received onto the first adhesive layer 11 individually or in multiple batches at once. Figure 3 (c) A cross-sectional schematic diagram showing the shape of all electronic components 21 on the cutting tape 20 being received on the adhesive surface of the first adhesive layer 11 of the transfer double-sided adhesive sheet 1.
[0238] Figure 4 This is a cross-sectional schematic diagram illustrating the second step in a method for mounting electronic components onto a mounting substrate using the double-sided adhesive sheet for transfer according to the present invention.
[0239] like Figure 4 As shown in (a), electronic components 21 arranged on the adhesive surface of the first adhesive layer 11 of the transfer double-sided adhesive sheet 1 are disposed opposite to and separated on the circuit surface 31 (circuit pattern omitted) of the mounting substrate 30. Next, as... Figure 4 As shown in (b), the circuit surface 31 of the mounting substrate 30 is brought close to the adhesive surface of the first adhesive layer 11 of the transfer double-sided adhesive sheet 1, so that the electronic component 21 contacts the circuit surface 31 of the mounting substrate 30.
[0240] The transfer of electronic component 21 onto the circuit surface 31 of mounting substrate 30 can be performed by heat pressing (e.g., 150°C for 1 minute). The substrate 10, the first adhesive layer 11 and / or the second adhesive layer 12 constituting the transfer double-sided adhesive sheet 1 have excellent heat resistance, so they are not prone to expansion, contraction or changes in adhesive force due to heat pressing, thus enabling the electronic component 21 to be transferred onto the circuit surface 31 of mounting substrate 30 with high precision.
[0241] Next, as Figure 4 As shown in (c), by separating the double-sided adhesive sheet 1 for transfer from the mounting substrate 30, the electronic component 21 is peeled off from the first adhesive layer 11 and transferred onto the circuit surface 31 of the mounting substrate 30. Since the first adhesive layer 11 is composed of a low-adhesion adhesive layer, the electronic component 21 is easy to peel off and can be efficiently mounted onto the mounting substrate 30 without damaging the electronic component 21.
[0242] After the electronic component 21 is mounted onto the mounting substrate 30 Figure 4 (c) The double-sided adhesive sheet 1 for transfer can be peeled off from the carrier substrate 22 (illustration omitted). Since the second adhesive layer 12 is made of a peelable adhesive layer, it can be peeled off without any glue residue, has excellent reworkability, and therefore the carrier substrate 22 can be easily reused.
[0243] As electronic components to be mounted on a mounting substrate, there are no particular restrictions, and fine and thin semiconductor chips and LED chips can be used appropriately.
[0244] Example
[0245] The present invention will be described in more detail below with reference to specific embodiments, but the present invention is not limited to these embodiments in any way.
[0246] [Manufacturing Example 1]: Manufacturing of acrylic copolymer (1)
[0247] 100 parts by weight of 2-ethylhexyl acrylate (2EHA) (manufactured by Nippon Shokubai Co., Ltd.), 4 parts by weight of 2-hydroxyethyl acrylate (HEA) (manufactured by Toa Synthetic Co., Ltd.), 0.02 parts by weight of 2,2'-azobisisobutyronitrile (manufactured by Wako Pure Chemical Industries, Ltd.) as a polymerization initiator and 180 parts by weight of ethyl acetate were added to a four-necked flask equipped with a stirring blade, a thermometer, a nitrogen inlet pipe and a condenser. Nitrogen gas was introduced while stirring slowly to maintain the liquid temperature in the flask at around 65°C and to carry out the polymerization reaction for 6 hours, thereby preparing a solution of acrylic copolymer (1) with a weight average molecular weight of 560,000 (solid content: 35% by weight).
[0248] [Manufacturing Example 2]: Manufacturing of acrylic copolymer (2)
[0249] 95 parts by weight of butyl acrylate (manufactured by Nippon Shokubai Co., Ltd.), 5 parts by weight of acrylic acid (manufactured by Toa Synthetic Co., Ltd.), 0.2 parts by weight of 2,2'-azobisisobutyronitrile (manufactured by Wako Pure Chemical Industries, Ltd.) as a polymerization initiator and 156 parts by weight of ethyl acetate were added to a four-necked flask equipped with a stirring blade, a thermometer, a nitrogen inlet pipe and a condenser. Nitrogen gas was introduced while stirring slowly to maintain the liquid temperature in the flask at around 63°C and to carry out the polymerization reaction for 10 hours, thereby preparing a solution of acrylic copolymer (2) with a weight average molecular weight of 700,000 (solid content: 40% by weight).
[0250] [Manufacturing Example 3]: Manufacturing of acrylic copolymer (3)
[0251] 2.8 parts by weight of 80% acrylic acid (AA) (manufactured by Osaka Organic Chemical Industry Co., Ltd.), 44 parts by weight of 2-ethylhexyl acrylate (2EHA) (manufactured by Nippon Shokubai Co., Ltd.), 35.2 parts by weight of vinyl acetate (manufactured by Denka Co., Ltd.), and 20 parts by weight of toluene were added to a four-necked flask equipped with a stirring blade, thermometer, nitrogen inlet pipe, and condenser. Nitrogen gas was introduced while stirring slowly, and the mixture was stirred for 1 hour. Then, 0.2 parts by weight of Nyper BW (manufactured by Nippon Yu Co., Ltd.), diluted with 96 parts by weight of toluene as a polymerization initiator, were added dropwise, and the liquid temperature in the flask was maintained at around 40°C. Then, the liquid temperature in the flask was raised to 60°C and the polymerization reaction was carried out for 8 hours. Then, the temperature was raised to 95°C and stirred for 4 hours, thereby preparing a solution of acrylic copolymer (3) with a weight average molecular weight of 560,000 (solid content: 35% by weight).
[0252] [Manufacturing Example 4]: Manufacturing of a carbamate adhesive composition (2)
[0253] The polyols used include 85 parts by weight of Preminol S3011 (manufactured by Asahi Glass Co., Ltd., Mn=10000), a polyol with three OH groups; 13 parts by weight of Sannix GP-3000 (manufactured by Sanyo Chemical Co., Ltd., Mn=3000), a polyol with three OH groups; 2 parts by weight of Sannix GP-1000 (manufactured by Sanyo Chemical Co., Ltd., Mn=1000), a polyol with three OH groups; 18 parts by weight of Coronate HX (manufactured by Nippon Polyurethane Industry Co., Ltd.), a polyfunctional alicyclic isocyanate compound; 0.1 parts by weight of a catalyst (manufactured by Nippon Chemical Industry Co., Ltd., trade name: NACEM Iron(III)); and 0.5 parts by weight of Irganox as an anti-deterioration agent. A carbamate adhesive composition (2) was prepared by adding 1010 (manufactured by BASF), 5 parts by weight of 2-ethylhexanoate cetyl ester (manufactured by Nissin Oriyo Group Co., Ltd., trade name: Salacos 816T, Mn=368) as a fatty acid ester and 0.2 parts by weight of Megaface F-571 (manufactured by DIC Co., Ltd.) as a fluorinated surfactant, ethyl acetate as a diluent, and mixing and stirring.
[0254] [Example 1]
[0255] (Making of double-sided adhesive sheet for transfer)
[0256] 100 parts by weight of silicone binder 1 (addition reaction type silicone binder, trade name "X-40-3306", manufactured by Shin-Etsu Chemical Industry Co., Ltd.), 1.4 parts by weight of platinum catalyst 1 (trade name "CAT-PL-50T", manufactured by Shin-Etsu Chemical Industry Co., Ltd.), and 5 parts by weight of silicone stripping agent 1 (addition reaction type silicone stripping agent with dimethyl polysiloxane as the main component, trade name "KS-776A", manufactured by Shin-Etsu Chemical Industry Co., Ltd.) were added, diluted with toluene to make the total solid content 25% by weight, and mixed using a disperser to prepare a silicone binder composition (silicone binder composition 1).
[0257] The silicone adhesive composition 1 was applied to the silicone-primed surface of a substrate film (1) (a 75 μm thick polyester film with one side treated with a silicone primer, trade name "Diafoil MRF#75", manufactured by Mitsubishi Resin Co., Ltd.) with a dried paste thickness of 10 μm. The mixture was then cured and dried at a drying temperature of 120°C for 5 minutes. In this manner, a film having a silicone adhesive layer (1) on the silicone primer layer of the substrate film (1) was obtained.
[0258] It should be noted that the spacer (1) (a polyethylene terephthalate film without peeling treatment, with a thickness of 25 μm, trade name "Lumirror S10#25", manufactured by Toray Industries, Inc.) is attached to the adhesive surface of the silicone adhesive film to protect the silicone adhesive layer, thereby obtaining a laminate (1) with a laminated structure of [spacer (1) layer] / [silicone adhesive (1) layer] / [substrate film (1) layer]].
[0259] Next, in the solution of the acrylic copolymer (1) obtained in Manufacturing Example 1, 4.0 parts by weight of Coronate HX (manufactured by Tosoh Corporation) as a crosslinking agent and 0.02 parts by weight of Embilizer OL-1 (manufactured by Tokyo Fine Chemicals Co., Ltd.) as a crosslinking catalyst were added relative to 100 parts by weight of its solid content. The mixture was diluted with toluene to make the total solid content 25% by weight. The acrylic adhesive composition stirred by a disperser was applied to the release layer side of the separator (2) (a 38 μm thick polyethylene terephthalate film with a release treatment, trade name "MRF#38", manufactured by Mitsubishi Chemical Corporation) with a thickness of 20 μm after drying using an impregnation roller. The mixture was cured and dried at a drying temperature of 130°C for 30 seconds. In this way, an acrylic adhesive layer (1) was formed on the separator (2).
[0260] Next, the substrate film (1) side (non-silicone primer treated side) of the above-obtained laminate (1) is attached to the surface of the acrylic adhesive layer (1), thereby obtaining a double-sided adhesive sheet for transfer with a laminate structure of [spacer (1) layer] / [silicone adhesive (1) layer (first adhesive layer)] / [substrate film (1) layer] / [acrylic adhesive (1) layer (second adhesive layer)] / [spacer (2) layer].
[0261] [Example 2]
[0262] Compared to 100 parts by weight of the solid content of the acrylic copolymer (2) obtained in Manufacturing Example 2, 6 parts by weight of TETRAD-C (manufactured by Mitsubishi Gas Chemical Co., Ltd.) as a crosslinking agent were added, and the mixture was diluted with ethyl acetate to make the total solid content 25% by weight. The acrylic adhesive composition was stirred using a disperser and coated onto the spacer (2). Otherwise, a double-sided adhesive sheet for transfer with a laminated structure of [spacer (1) layer] / [silicone adhesive (1) layer (first adhesive layer)] / [substrate film (1) layer] / [acrylic adhesive (2) layer (second adhesive layer)] / [spacer (2) layer] was obtained in the same manner as in Example 1.
[0263] [Example 3]
[0264] In the solution of the acrylic copolymer (1) obtained in Manufacturing Example 1, 4.0 parts by weight of Coronate L (manufactured by Tosoh Corporation) was added instead of Coronate HX as a crosslinking agent, relative to 100 parts by weight of its solid content. Otherwise, a double-sided adhesive sheet for transfer with a laminated structure of [spacer (1) layer] / [silicone adhesive (1) layer (first adhesive layer)] / [substrate film (1) layer] / [acrylic adhesive (3) layer (second adhesive layer)] / [spacer (2) layer] was obtained in the same manner as in Example 1.
[0265] [Example 4]
[0266] In the solution of the acrylic copolymer (3) obtained in Manufacturing Example 3, TETRAD-C (manufactured by Mitsubishi Gas Chemical Co., Ltd.) as a crosslinking agent was added to 100 parts by weight of its solid content, based on the solid content. The solution was diluted with methyl ethyl ketone to make the total solid content 25% by weight. The solution was stirred using a disperser and the resulting acrylic adhesive composition was coated onto the separator (2). Otherwise, a double-sided adhesive sheet for transfer with a laminated structure of [separator (1) layer] / [silicone adhesive (1) layer (first adhesive layer)] / [substrate film (1) layer] / [acrylic adhesive (4) layer (second adhesive layer)] / [separator (2) layer] was obtained in the same manner as in Example 1.
[0267] [Example 5]
[0268] In a solution of Cyabine SH-109 (manufactured by Toyo Komi Co., Ltd.), which is a prepolymer-type urethane adhesive composition (1), 4.0 parts by weight of Coronate HX (manufactured by Tosoh Co., Ltd.) as a crosslinking agent, 10 parts by weight of Salacos 913 (manufactured by Nissin Oriyo Co., Ltd.) as a light peeling agent, 1 part by weight of Megaface F-571 (manufactured by DIC Co., Ltd.) as a fluorinated surfactant, and 0.5 parts by weight of Irgacure 1010 (manufactured by BASF) as an anti-deterioration agent were added relative to 100 parts by weight of its solid content. The solution was diluted with ethyl acetate to make the total solid content 20% by weight. The solution was stirred using a disperser and coated onto a substrate film (2) (untreated PET film, 75 μm thick, trade name "Lumirror") to a thickness of 20 μm after drying. On S10#75”, manufactured by Toray Industries, Inc., the film was cured and dried at a drying temperature of 130°C and a drying time of 30 seconds. A spacer (2) (a polyethylene terephthalate film with a thickness of 38 μm that has undergone peeling treatment, trade name “MRF#38”, manufactured by Mitsubishi Chemical Corporation) was attached to the adhesive surface of the obtained urethane adhesive film to protect the urethane adhesive layer. Otherwise, a double-sided adhesive sheet for transfer with a laminated structure of [spacer (2) layer] / [urethane adhesive (1) layer (first adhesive layer)] / [substrate film (2) layer] / [acrylic adhesive (1) layer (second adhesive layer)] / [spacer (2) layer] was obtained in the same manner as in Example 1.
[0269] [Comparative Example 1]
[0270] Compared to 100 parts by weight of the solid content of the acrylic copolymer (2) obtained in Manufacturing Example 2, 0.01 parts by weight of TETRAD-C (manufactured by Mitsubishi Gas Chemical Co., Ltd.) as a crosslinking agent was added, diluted with ethyl acetate to make the total solid content 25% by weight. The mixture was stirred using a disperser and coated onto the spacer (2). Otherwise, a double-sided adhesive sheet for transfer with a laminated structure of [spacer (1) layer] / [silicone adhesive (1) layer (first adhesive layer)] / [substrate film (1) layer] / [acrylic adhesive (5) layer (second adhesive layer)] / [spacer (2) layer] was obtained in the same manner as in Example 1.
[0271] [Comparative Example 2]
[0272] A thermosetting polyurethane resin film (manufactured by Toray Industries, Inc., which is obtained by protecting a 100 μm thick polyurethane resin film (100% modulus = 32 MPa) with a 50 μm thick surface protective film) was used instead of the laminate (1). Otherwise, a double-sided adhesive sheet for transfer with a laminate structure of [surface protective film layer] / [polyurethane resin film layer] / [acrylic adhesive (1) layer (second adhesive layer)] / [spacer (2) layer] was obtained in the same manner as in Example 1.
[0273] [Comparative Example 3]
[0274] The acrylic adhesive composition used in Example 1 was used instead of the silicone adhesive composition 1 and coated on the substrate film (2) (untreated PET film, 75 μm thick, trade name "Lumirror S10#75", manufactured by Toray Industries, Inc.) with a dry thickness of 20 μm. It was cured and dried at a drying temperature of 130°C and a drying time of 30 seconds. A spacer (2) (a peel-treated polyethylene terephthalate film, 38 μm thick, trade name "MRF#38", manufactured by Mitsubishi Chemical Corporation) was attached to the adhesive surface of the resulting acrylic adhesive film to protect the acrylic adhesive layer. Otherwise, a transfer double-sided adhesive sheet with a laminated structure of [spacer (2) layer] / [acrylic adhesive (1) layer (first adhesive layer)] / [substrate film (2) layer] / [acrylic adhesive (1) layer (second adhesive layer)] / [spacer (2) layer] was obtained in the same manner as in Example 1.
[0275] [Comparative Example 4]
[0276] The acrylic adhesive composition used in Example 2 was used instead of the silicone adhesive composition 1 and coated on the substrate film (2) (untreated PET film, 75 μm thick, trade name "Lumirror S10#75", manufactured by Toray Industries, Inc.) with a dry thickness of 20 μm. It was cured and dried at a drying temperature of 130°C and a drying time of 30 seconds. A spacer (2) (a peel-treated polyethylene terephthalate film, 38 μm thick, trade name "MRF#38", manufactured by Mitsubishi Chemical Corporation) was attached to the adhesive surface of the resulting acrylic adhesive film to protect the acrylic adhesive layer. Otherwise, a transfer double-sided adhesive sheet with a laminated structure of [spacer (2) layer] / [acrylic adhesive (2) layer (first adhesive layer)] / [substrate film (2) layer] / [acrylic adhesive (1) layer (second adhesive layer)] / [spacer (2) layer] was obtained in the same manner as in Example 1.
[0277] [Comparative Example 5]
[0278] The acrylic adhesive composition used in Example 3 was used instead of the silicone adhesive composition 1 and coated on the substrate film (2) (untreated PET film, 75 μm thick, trade name "Lumirror S10#75", manufactured by Toray Industries, Inc.) with a dry thickness of 20 μm. It was cured and dried at a drying temperature of 130°C and a drying time of 30 seconds. A spacer (2) (a peel-treated polyethylene terephthalate film, 38 μm thick, trade name "MRF#38", manufactured by Mitsubishi Chemical Corporation) was attached to the adhesive surface of the resulting acrylic adhesive film to protect the acrylic adhesive layer. Otherwise, a transfer double-sided adhesive sheet with a laminated structure of [spacer (2) layer] / [acrylic adhesive (3) layer (first adhesive layer)] / [substrate film (2) layer] / [acrylic adhesive (1) layer (second adhesive layer)] / [spacer (2) layer] was obtained in the same manner as in Example 1.
[0279] [Comparative Example 6]
[0280] The acrylic adhesive composition used in Example 4 was used instead of the silicone adhesive composition 1 and coated on the substrate film (2) (untreated PET film, 75 μm thick, trade name "Lumirror S10#75", manufactured by Toray Industries, Inc.) with a dry thickness of 20 μm. It was cured and dried at a drying temperature of 130°C and a drying time of 30 seconds. A spacer (2) (a peel-treated polyethylene terephthalate film, 38 μm thick, trade name "MRF#38", manufactured by Mitsubishi Chemical Corporation) was attached to the adhesive surface of the resulting acrylic adhesive film to protect the acrylic adhesive layer. Otherwise, a transfer double-sided adhesive sheet with a laminated structure of [spacer (2) layer] / [acrylic adhesive (4) layer (first adhesive layer)] / [substrate film (2) layer] / [acrylic adhesive (1) layer (second adhesive layer)] / [spacer (2) layer] was obtained in the same manner as in Example 1.
[0281] [Comparative Example 7]
[0282] The urethane adhesive composition (2) obtained in Manufacturing Example 4 was coated onto a substrate film (2) (untreated PET film, 75 μm thick, trade name "Lumirror S10#75", manufactured by Toray Industries, Inc.) with a dried thickness of 20 μm. It was cured and dried at a drying temperature of 130°C and a drying time of 30 seconds. A spacer (2) (a peel-treated polyethylene terephthalate film, 38 μm thick, trade name "MRF#38", manufactured by Mitsubishi Chemical Corporation) was attached to the adhesive surface of the obtained urethane adhesive film to protect the urethane adhesive layer. Otherwise, a transfer double-sided adhesive sheet with a laminated structure of [spacer (2) layer] / [urethane adhesive (2) layer (first adhesive layer)] / [substrate film (1) layer] / [acrylic adhesive (1) layer (second adhesive layer)] / [spacer (2) layer] was obtained in the same manner as in Example 1.
[0283] <Evaluation>
[0284] The transfer double-sided adhesive sheets obtained in the examples and comparative examples were evaluated as follows. The results are shown in Tables 3 and 4.
[0285] (Capture Feature)
[0286] For bare silicon wafers (process: CZ, conductivity type: P, impurities: B, thickness: 750 μm, resistivity: 1 Ωcm~50 Ωcm, surface: mirror, back side: mirror, crystal orientation (100), surface impurities: Fe, Ni, Cu, Zn, Cr, Al, Na < 1.0 (×10) 10 atoms / cm 2 Back-side grinding was performed under the conditions shown in Table 1 below to achieve a thickness of 500 μm. The mask material was then applied to the back-ground wafer surface using a manual roller without air bubbles. It should be noted that the mask material was applied in a manner that covered the entire Si wafer.
[0287] Next, ultraviolet light was irradiated from the substrate side of the mask material under the following ultraviolet irradiation conditions to cure the adhesive layer of the mask material. Then, the dicing / die-bonding film (DU-2495KS, manufactured by Nitto Denko Corporation) was adhered to the back side of the wafer. A dicing ring for dicing was adhered to the adhesive surface of the dicing tape. After adhesion, it was placed at 22°C for 30 minutes under light-shielding conditions. Then, the mask material was peeled off, and the Si wafer and dicing tape were diced by blade cutting under the conditions shown in Table 2 below, thereby preparing a dicing / die-bonding film with multiple silicon chips arranged and fixed with one side measuring 1 mm square.
[0288] After cutting, the bare Si wafer is irradiated with ultraviolet light from the substrate side of the cutting tape under the following conditions.
[0289] <Ultraviolet Irradiation Conditions>
[0290] Ultraviolet irradiation device: Manufactured by Nitto Seiki Co., Ltd., Product name: UM810
[0291] Light source: High-pressure mercury lamp
[0292] Irradiation intensity: 50mW / cm 2 (Measuring equipment: Ushio Corporation, product name "UT-101 UV illuminometer")
[0293] Irradiation time: 6 seconds
[0294] Cumulative light intensity: 300 mJ / cm 2
[0295] [Table 1]
[0296]
[0297] [Table 2]
[0298]
[0299] Using the same method, the first adhesive layer of the transfer double-sided adhesive sheet is attached to the cutting ring with the first adhesive layer as the surface, and the spacer (1) of the first adhesive layer is peeled off. The double-sided adhesive sheet is cut to a depth of 30 μm to the surface of the double-sided adhesive sheet using the same method as shown in Table 2, thereby producing a marked transfer double-sided adhesive sheet that is paired with a cutting / die bonding film of multiple silicon chips with one side 1 mm square.
[0300] With the silicon chip with the adhesive layer fixed to the cut / die bonded film obtained above placed face down, the first adhesive layer of the transfer double-sided adhesive sheet (an adhesive sheet marked on the first adhesive layer side of the substrate) obtained in the examples and comparative examples is placed face up and positioned relative to it with a gap of 1 mm. The marks are aligned, and the silicon chip with the adhesive layer is pushed from the top (back side) of the cut / die bonded film using a needle, so that 10 silicon chips fall onto the adhesive surface of the first adhesive layer.
[0301] Visually inspect all fallen silicon chips to confirm that they fell accurately to the marked positions and without flipping, and evaluate them according to the following criteria.
[0302] 〇……All silicon chips fall without shifting or flipping relative to the markings.
[0303] △... More than 5 silicon chips fall without shifting or flipping relative to the mark.
[0304] ...All the silicon chips fell after their positions were shifted or flipped relative to the markers.
[0305] (Adhesive force)
[0306] <Determination of the initial adhesion force of the first adhesive layer to the PET film>
[0307] The double-sided adhesive sheets used for transfer printing in the examples and comparative examples were cut into pieces with a width of 25 mm and a length of 150 mm, and used as evaluation samples.
[0308] The spacer of the second adhesive layer was peeled off, and the surface of the second adhesive layer was adhered to a glass plate (manufactured by Matsunami Glass Industry Co., Ltd., trade name: Micro slide glass S). Then, a PET film cut to a width of 20 mm and a length of 100 mm (trade name: Lumirror S10#25 (manufactured by Toray Industries, Inc.)) was adhered to the first adhesive layer after the spacer was peeled off by rolling a 2.0 kg roller once at 23°C and 50% RH. After curing at 23°C and 50% RH for 30 minutes, the film was peeled off using a universal tensile testing machine (manufactured by Minebea Corporation, product name: TCM-1kNB) at a peel angle of 180 degrees and a tensile speed of 300 mm / min, and the adhesive strength was measured.
[0309] <Determination of the adhesion strength of the first adhesive layer to the PET film after 160°C and 5 minutes>
[0310] The double-sided adhesive sheets used for transfer printing in the examples and comparative examples were cut into pieces with a width of 25 mm and a length of 150 mm, and used as evaluation samples.
[0311] The spacer of the second adhesive layer is peeled off, and the adhesive layer surface is adhered to the glass plate (manufactured by Matsunami Glass Industry Co., Ltd., trade name: Micro slide glass S). Then, a PET film cut to a width of 20mm and a length of 100mm (trade name: Lumirror S10#25 (manufactured by Toray Industries, Inc.)) is adhered to the first adhesive layer after the spacer has been peeled off by rolling a 2.0kg roller once at 23°C and 50% RH. Curing is then carried out at 23°C and 50% RH for 30 minutes.
[0312] Next, heat in an air-circulating constant temperature oven at 160°C for 5 minutes and remove. Then, allow to cool naturally at 23°C and 50% RH for 30 minutes, and then peel using a universal tensile testing machine (manufactured by Minebea Corporation, product name: TCM-1kNB) at a peel angle of 180 degrees and a tensile speed of 300 mm / min, and measure the adhesive strength.
[0313] <Determination of the initial adhesion force of the second adhesive layer to the glass plate>
[0314] The transfer double-sided sheets of the examples and comparative examples were cut into pieces with a width of 25 mm and a length of 150 mm, and used as evaluation samples.
[0315] The second adhesive layer surface of the evaluation sample, after the spacer was peeled off, was adhered to a glass plate (manufactured by Matsunami Glass Industry Co., Ltd., trade name: Micro slideglass S) by reciprocating once with a 2.0 kg roller at 23°C and 50% RH. After curing for 30 minutes at 23°C and 50% RH, peeling was performed using a universal tensile testing machine (manufactured by Minebea Co., Ltd., product name: TCM-1kNB) at a peel angle of 180 degrees and a tensile speed of 300 mm / min, and the adhesive strength was measured.
[0316] <Determination of the adhesion strength of the second adhesive layer to the glass plate after 5 minutes at 160°C>
[0317] The double-sided adhesive sheets used for transfer printing in the examples and comparative examples were cut into pieces with a width of 25 mm and a length of 150 mm, and used as evaluation samples.
[0318] The second adhesive layer, after the spacer was removed, was adhered to a glass plate (manufactured by Matsunami Glass Industry Co., Ltd., trade name: Micro slideglass S) by reciprocating a 2.0 kg roller once at 23°C and 50% RH. The plate was then cured for 30 minutes at 23°C and 50% RH.
[0319] Next, heat in an air-circulating constant temperature oven at 160°C for 5 minutes and remove. Then, allow to cool naturally at 23°C and 50% RH for 30 minutes, and then peel using a universal tensile testing machine (manufactured by Minebea Corporation, product name: TCM-1kNB) at a peel angle of 180 degrees and a tensile speed of 300 mm / min, and measure the adhesive strength.
[0320] (Adhesion)
[0321] The double-sided adhesive sheets used for transfer printing in the examples and comparative examples were cut into pieces with a width of 20 mm and a length of 50 mm, and used as evaluation samples.
[0322] The adhesive layer of the non-tested side of the evaluation sample was adhered to a glass plate (Matsunami Glass Industry Co., Ltd., trade name: Micro slide glass S) using a manual roller. Next, the spacer attached to the test surface was peeled off, and the adhesion (gf / 5mmΦSUS) was measured using an adhesion testing machine (RHESCA Co., Ltd., product name: TAC-II) under the following conditions.
[0323] <Measurement Conditions>
[0324] Probe: 5mm ΦSUS
[0325] Pressing / drawing speed: 120mm / min
[0326] Indentation load: 100gf
[0327] Contact time: 3 seconds
[0328] (Surface force)
[0329] The double-sided adhesive sheets used for transfer printing in the examples and comparative examples were cut into 10mm wide and 10mm long pieces and used as evaluation samples.
[0330] The adhesive layer of the non-tested surface of the evaluation sample was attached to a glass plate (manufactured by Matsunami Glass Industry Co., Ltd., trade name: Micro slide glass S) using a manual roller. Then, the septum of the surface to be tested was peeled off, and the surface force (μN) was measured using an ultra-micro indentation hardness tester (manufactured by ELIONIX, product name: ENT-NEXUS) under the following conditions.
[0331] <Measurement Conditions>
[0332] Indenter used: Glass ball probe (manufactured by ELIONIX, diameter: 1mm, BK7)
[0333] Atmosphere measurement: in the atmosphere
[0334] Measurement temperature: 30℃
[0335] (Surface roughness)
[0336] The surface roughness of the film was measured using a contact optical roughness measuring instrument (Zygo New View 7300) with an objective lens of 50x and an internal lens of 2x (measurement field (XY): 70μm × 50μm). The samples were subjected to High Pass treatment, and the values of Ra, Rz, and Rms were measured at three locations. The average value was taken as the measured value.
[0337] (Storage modulus, loss modulus)
[0338] The first adhesive layer of the transfer double-sided adhesive sheet of the examples and comparative examples was observed and measured using an AFM (manufactured by Bruker AXS, product name "NanoScope V / Dimension Icon"), and the storage modulus and loss modulus at 1 Hz and 1 kHz at 25°C were determined. The measurement mode was AFM·DMA mode, and the measurements were performed under the following conditions.
[0339] <Measurement Settings>
[0340] Measurement area: 5μm × 5μm
[0341] Number of measurement points: 32×32
[0342] Actuator: 1kHz~20kHz scan
[0343] (Glass reworkability)
[0344] In the test of the adhesion force of the second adhesive layer to the glass plate at 160°C for 5 minutes, the glass workability was judged according to the following criteria.
[0345] 〇: Below 3N / 25mm
[0346] △: Greater than 3N / 25mm and less than or equal to 5N / 25mm
[0347] ×: Greater than 5N / 25mm
[0348] (Transferability)
[0349] In the test of the adhesion of the first adhesive layer to the PET film at 160°C for 5 minutes, the transferability was judged according to the following criteria.
[0350] 〇: Below 1000mN / 25mm
[0351] △: Greater than 1000 N / 25 mm and less than 5000 mN / 25 mm
[0352] ×:5000mN or more / 25mm
[0353]
[0354] [Table 4]
[0355]
[0356] The following are variations of the present invention.
[0357] [Appendix 1] A double-sided adhesive sheet for transfer printing, wherein the double-sided adhesive sheet for transfer printing is obtained by laminating a first adhesive layer, a substrate, and a second adhesive layer in this order, wherein...
[0358] The first adhesive layer mentioned above includes a low-adhesion adhesive layer.
[0359] The second adhesive layer described above includes a peelable adhesive layer.
[0360] [Note 2] As described in Note 1, the double-sided adhesive sheet for transfer has a storage modulus of 50 MPa or less at a frequency of 1 Hz and 25°C as measured by AFM-DMA.
[0361] [Note 3] The double-sided adhesive sheet for transfer as described in Note 1 or 2, wherein the energy storage modulus of the first adhesive layer at a frequency of 1 kHz and 25°C as measured by AFM-DMA is 100 MPa or less.
[0362] [Appendix 4] The double-sided adhesive sheet for transfer as described in any one of Appendices 1 to 3, wherein the ratio of the energy storage modulus of the first adhesive layer at a frequency of 1 kHz and 25°C measured using AFM-DMA to the energy storage modulus of the first adhesive layer at a frequency of 1 Hz and 25°C measured using AFM-DMA is greater than 1.
[0363] [Note 5] The transfer double-sided adhesive sheet as described in any one of Notes 1 to 4, wherein the loss modulus of the first adhesive layer at a frequency of 1 Hz and 25°C as measured by AFM-DMA is 7 MPa or less.
[0364] [Note 6] The double-sided adhesive sheet for transfer as described in any one of Notes 1 to 5, wherein the adhesion of the first adhesive layer to the stainless steel plate (5 mm in diameter) is 10 gf / Φ5 mm SUS to 250 gf / Φ5 mm SUS.
[0365] [Note 7] The double-sided adhesive sheet for transfer as described in any one of Notes 1 to 6, wherein the substrate comprises a heat-resistant resin.
[0366] [Appendix 8] A method for mounting electronic components onto a mounting substrate, wherein the method comprises the following steps:
[0367] The process of receiving the cut electronic components with the first adhesive layer of the transfer double-sided adhesive sheet as described in any one of Appendices 1 to 7; and
[0368] The process of transferring the electronic components received by the first adhesive layer onto the mounting substrate.
[0369] [Note 9] The method as described in Note 8, wherein a carrier substrate is adhered to the second adhesive layer of the above-mentioned double-sided adhesive sheet for transfer.
[0370] [Note 10] The method as described in Note 8 or 9, wherein the electronic component is a semiconductor chip.
[0371] Label Explanation
[0372] 1. Double-sided adhesive sheet for transfer printing
[0373] 10 Substrate
[0374] 11 First adhesive layer
[0375] 12 Second adhesive layer
[0376] 110, 120 spacers
[0377] 20 Cutting tape
[0378] 21 Electronic Components
[0379] 22 Carrier substrate
[0380] 23. Ejector pin components
[0381] 30 Mounting substrate
[0382] 31 Circuit Surface
Claims
1. A double-sided adhesive sheet for transfer printing, wherein the double-sided adhesive sheet for transfer printing is obtained by laminating a first adhesive layer, a substrate, and a second adhesive layer in this order, wherein, The first adhesive layer comprises a low-adhesion adhesive layer. The second adhesive layer includes a peelable adhesive layer. The second adhesive layer exhibits relatively higher adhesive strength compared to the first adhesive layer. The first adhesive layer is an adhesive layer used to receive and hold electronic components and to transfer the electronic components onto the mounting substrate. The first adhesive layer is composed of at least one adhesive selected from the group consisting of silicone adhesives, urethane adhesives, acrylic adhesives, rubber adhesives, polyester adhesives, polyamide adhesives, epoxy adhesives, vinyl alkyl ether adhesives, and fluorinated adhesives. The first adhesive layer has a peel strength of 0.1 mN / 25 mm or more against the PET film at 25°C and a 180° peel angle. The thickness of the first adhesive layer is more than 1 μm and less than 100 μm. The second adhesive layer is composed of at least one adhesive selected from the group consisting of silicone adhesives, urethane adhesives, acrylic adhesives, rubber adhesives, polyester adhesives, polyamide adhesives, epoxy adhesives, vinyl alkyl ether adhesives, and fluorinated adhesives. The second adhesive layer has a 180° peel bond strength to the glass plate at 25°C of 1mN / 25mm to 5000mN / 25mm.
2. The double-sided adhesive sheet for transfer as described in claim 1, wherein, The energy storage modulus of the first adhesive layer at a frequency of 1 Hz and 25°C, as measured by AFM-DMA, is less than 50 MPa.
3. The double-sided adhesive sheet for transfer as described in claim 1 or 2, wherein, The energy storage modulus of the first adhesive layer, measured using AFM-DMA at a frequency of 1 kHz and a temperature of 25°C, is less than 100 MPa.
4. The double-sided adhesive sheet for transfer as described in claim 1 or 2, wherein, The ratio of the energy storage modulus of the first adhesive layer at a frequency of 1 kHz and 25°C, as measured by AFM-DMA, to the energy storage modulus of the first adhesive layer at a frequency of 1 Hz and 25°C, as measured by AFM-DMA, is greater than 1.
5. The double-sided adhesive sheet for transfer as described in claim 1 or 2, wherein, The loss modulus of the first adhesive layer at a frequency of 1 Hz and 25°C, as measured by AFM-DMA, is below 7 MPa.
6. The double-sided adhesive sheet for transfer as described in claim 1 or 2, wherein, The adhesion of the first adhesive layer to a stainless steel plate with a diameter of 5mm is 10gf / Φ5mmSUS to 250gf / Φ5mmSUS.
7. The double-sided adhesive sheet for transfer as described in claim 1 or 2, wherein, The substrate comprises a heat-resistant resin, which comprises at least one selected from the group consisting of polyimide, polyethylene terephthalate, polyethylene naphthalate, polyamide, and polyetheretherketone.
8. A method for mounting electronic components onto a mounting substrate, wherein, The method for mounting electronic components onto a mounting substrate includes the following steps: The step of receiving the cut electronic component in the first adhesive layer of the double-sided adhesive sheet for transfer as described in any one of claims 1 to 7; and The process of transferring the electronic components received by the first adhesive layer onto the mounting substrate.
9. The method for mounting electronic components onto a mounting substrate as described in claim 8, wherein, A carrier substrate is attached to the second adhesive layer of the double-sided adhesive sheet for transfer.
10. The method of mounting electronic components onto a mounting substrate as described in claim 8 or 9, wherein, The electronic component is a semiconductor chip.
Citation Information
Patent Citations
Adhesive metal sheet for fixing semiconductor wafer
JP1985196956A
Dicing die-bonding film
JP2019009203A
Pasting method for electronic part and formation method for ditching on adhesive tape
JP2001085360A
Double-sided pressure-sensitive adhesive sheet and transfer method for brittle member
JP2005263876A
Temperature-sensitive adhesive tape for touch sensor transfer
JP2017031331A
